Effects of Cholesterol and Solution pH on Daptomycin-bilayer Interactions - Samuel R. Pennock; Maggie Cortes; Megha D. Salecha; Neil X. Sevilla; Nicole R. Rementer; Kevin Rana; Luke C. Hicks; Emmaleigh Fox; Ahmed Grine; Patience S. Hammel; Timothy D. Vaden; Benjamin R. Carone; et al. (The Journal of Membrane Biology, 2026)

Biogeomorphic significance of Middle Jurassic vegetation-induced sedimentary structures (VISS) in the Murihuku terrane, South Island, New Zealand - Neil S. Davies; James A. Craig; William J. McMahon; Anthony P. Shillito; Yorick P. Veenma; Mike Pole (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Process-based ecosystem modelling to strengthen forest valuation under climate and carbon: Linking ecology, disturbance risk and management decisions - Daniel S. Mendham; Philip J. Smethurst; Jim O’Hehir; Neil Huth; Ron Taylor; Ning Liu; Tiemen Rhebergen (Forest Ecology and Management, 2026)

Life in a Permian dryland: Evidence from plant and trace fossils of the fluvio-aeolian Cap-aux-Meules Formation (Îles-de-la-Madeleine, Québec) - James A. Craig; Neil S. Davies; Lorenzo Marchetti (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Exercise-induced compensation and C-reactive protein change in adults with elevated C-reactive protein: analysis of a randomised controlled trial - James L. Dorling; John W. Apolzan; Diana M. Thomas; Christoph Höchsmann; Neil M. Johannsen; Robert Ross; Tim S. Church; Corby K. Martin (European Journal of Applied Physiology, 2026)
Purpose Exercise can reduce C-reactive protein (CRP), but heterogeneity exists and it is unclear whether exercise-induced weight compensation occurs or relates to CRP change. We examined whether compensation occurs in adults with elevated CRP during exercise and whether compensation and compensatory behaviours are associated with CRP change. Methods In this 4-month randomised controlled trial, 124 sedentary adults with elevated CRP (mean ± SD: 4.3 ± 2.5 mg/L) were randomised to a control group or a supervised aerobic exercise group expending 16 kcal/kg/week. Predicted weight change was estimated, and weight compensation (weight change – predicted weight change) was calculated. CRP was measured, and energy intake and non-exercise step count were assessed using questionnaires and pedometers, respectively. Results Weight compensation was greater in the exercise group than the control group (1.3 [95% CI, 0.6, 2.1] vs. 0.1 [95% CI, -0.6, 0.9] kg; P = 0.029). In response to exercise, compensation did not differ between participants with moderately higher (≤ 3 mg/L) and higher (> 3 mg/L) CRP ( P = 0.977). Exercisers who did not compensate exhibited a 1.2 (95% CI, 0.2, 2.2) mg/L reduction in CRP versus those who did compensate ( P = 0.016). Higher energy intake was associated with CRP change in exercisers, with each 100 kcal/day elevation in energy intake associated with a 0.1 (95% CI, 0.0, 0.2) mg/L increase in CRP ( P = 0.022). Conclusion Exercise-induced weight compensation occurs in adults with elevated CRP and is associated with attenuated improvements in CRP. Increased energy intake was associated with higher CRP in exercisers, suggesting that limiting increases in energy intake may enhance exercise-induced anti-inflammatory benefits. Clinical trials registration NCT00113061.

Residency and Space Use of Endangered Smoothhound Sharks ( Mustelus mustelus ) in Relation to Marine Protection and Demersal Longline Fishing Along South Africa's South Coast - Eugin Bornman; Taryn S. Murray; Neil Hammerschlag; Enrico Gennari (Fisheries Management and Ecology, 2026)
Shark populations are declining globally and the effectiveness of marine protected areas (MPAs) as a conservation tool may vary by species and environmental context. This study assessed space use and residency of smoothhound sharks ( Mustelus mustelus )—an endangered, yet highly exploited shark—in relation to spatial protection and fishing risk across three areas off the southern coast of South Africa. Passive acoustic telemetry data (2016–2023) from 37 individual sharks were analysed using residency indices and generalised additive models. Smoothhounds exhibited high site fidelity, with small daily home ranges ( 2 ). Residency showed a weak but significant negative relationship with fishing risk, indicating reduced residency in areas of higher fishing pressure. Residency was consistently higher within a MPA and adjacent bay waters, as compared to a nearby unprotected bay. These findings suggest that smoothhounds may respond to spatial protection and suggest that extending protection to the MPA‐adjacent high‐use areas could enhance conservation outcomes.

The mourning gecko Lepidodactylus lugubris as a model system for advancing invasion science - Neil Angelo S. Abreo; Ismael Soto; Phillip J. Haubrock (Journal for Nature Conservation, 2026)

Loss and Transformation of Coastal Wetlands due to Global Change in the Conterminous United States: Past, Present, and Future - Michael J. Osland; Bogdan Chivoiu; Kevin J. Buffington; Kristin B. Byrd; Joel A. Carr; Judith Z. Drexler; Nicholas M. Enwright; Neil K. Ganju; James. B. Grace; Eric E. Grossman; Glenn R. Guntenspergen; Kurt P. Kowalski; et al. (Wetlands, 2026)
Coastal wetlands are being transformed by global change, impacting the ecological and societal benefits provided by these ecosystems. Synthesizing knowledge of historical and expected future transformations in coastal wetlands can help inform forward-looking planning and stewardship efforts. Here, we review anticipated future ecological transformations in coastal wetlands of the conterminous United States and contrast them with past transformations. We examine trends at the national scale but focus in detail on the following six wetland-rich regions: (1) Everglades, (2) Mississippi River delta, (3) Chesapeake Bay, (4) San Francisco Estuary, (5) Puget Sound, and (6) Great Lakes. This review is among the first to integrate and compare coastal wetland transformations in the Great Lakes with their oceanic counterparts. Between 1850 and 1970, wetland losses across the nation were high because coastal wetlands were viewed as flooded wastelands needing to be drained, filled, or excavated to make room for other land uses. Over the last 50 years, growing public and scientific appreciation of the ecological and societal benefits provided by coastal wetlands has fostered tremendous gains in wetland restoration and legal protection. Looking to the future, climate change and accelerated sea-level rise have become critical threats to coastal wetlands and are emerging as major drivers of ecological loss and transformation. This review synthesizes regional knowledge regarding past, present, and future changes to help coastal scientists, environmental managers, and the public better anticipate and prepare for future coastal wetland transformations due to climate change, accelerated sea-level rise, land-use change, and other aspects of global change.

Quantifying user variability in the traditional X‐ray ice‐rafted‐debris counting technique - Neil McDonald; Tom Bradwell; S. Louise Callard; Jaime L. Toney (Journal of Quaternary Science, 2026)
The flux of icebergs is most commonly constrained in the palaeo‐record by manually counting gravel clasts in sediment core X‐ray images—a trusted method in Quaternary science and palaeoceanography for nearly 40 years. In this study, we explore the reproducibility (user consistency and between‐user variability) of the traditional clast‐counting technique, something that has rarely been quantified. A participatory study was undertaken whereby 14 individuals counted gravel clasts (>2 mm) on X‐radiographs in cm intervals of two different glaciomarine sediment cores: (i) a matrix‐supported subaqueous diamicton facies and (ii) a clast‐poor to clast‐moderate laminated facies. Pairwise comparisons of all 14 users' counts using Spearman's rho indicate statistically significant relationships in all but one case ( p p

Collaborative tools to optimise linear infrastructure vegetation for regional habitat connectivity - Nicholas A. Cork; Emma J.S. Ferranti; Neil Strong; Daniel L. Donaldson; Rachel S. Fisher; Andrew D. Quinn (Transportation Research Part D: Transport and Environment, 2026)

Erwinia amylovora amino acid auxotrophy and epiphytic growth on apple stigmas - Neil P. Schultes; Judith P. Sinn; Eric S. Swenson; Louis Orifice; Cameron Ryan; Timothy W. McNellis (Physiological and Molecular Plant Pathology, 2026)

Worldwide Invasions of Centrarchidae: The Dark Side of the Sunfish Family - Neil Angelo Abreo; Jonathan Tibo; António Barbosa Nogueira; Athanasios Nikolaou; Cüneyt Kaya; Ali Serhan Tarkan; Irmak Kurtul; Stelios Katsanevakis; Ronaldo Sousa; Teun Everts; Emili García‐Berthou; John S. Hargrove; et al. (Fish and Fisheries, 2026)
Freshwater fish invasions are major drivers of global ecological change, disrupting native biodiversity and ecosystem functions. However, many invasive fish hold significant socioeconomic value, resulting in conflict over their management. Centrarchidae, which are globally distributed and are important for sportfishing and aquaculture, are now potentially becoming a global threat. Yet, no comprehensive appraisal exists across taxa and regions integrating taxonomy, pathways, impacts and risk analysis for Centrarchidae. To address these gaps, we compiled published literature and leveraged publicly available databases to critically evaluate the current global status of non‐native Centrarchidae, finding 30 species established outside their native ranges with 17 being outside of North America. Largemouth bass ( Micropterus nigricans ) and pumpkinseed ( Lepomis gibbosus ) are the most widely introduced centrarchids. Reported impacts of Centrarchidae introduction are mostly ecological, with predation, competition, hybridisation, and disease transmission as major mechanisms. Conversely, socio‐economic and cultural effects are underreported. Currently, only ten species have undergone rapid risk screening, with 90% flagged as high risk. However, risk analyses remain sparse, confounded by taxonomic uncertainties (including hybridisation) and context dependence of impacts. With the changing climate and other anthropogenic disturbances in freshwaters, habitat suitability is expanding for centrarchids. Although concerning, Centrarchidae form a highly human‐mediated invasion complex with predictable pathways and tractable leverage points, so limiting propagule pressure and standardizing assessments can curb their future spread while informing balanced and evidence‐based fisheries policy that reconciles socioeconomic benefits with environmental costs.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Lung function and inflammation in healthy young adults after 6.6 hours of 0.07 ppm ozone exposure - Edward R. Pennington; Jairus C. Pulczinski; Martin W. Case; Jacob S. Griffin; Neil E. Alexis; Ilona Jaspers; Carole Robinette; Ann Chelminski; Andrea Davis; Neena Miller; David B. Peden; Andrew J. Ghio; et al. (Environmental Research, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Isotope composition of groundwater and surface waters at the vicinity of abandoned mercury mine in Puerto Princesa City, The Philippines - Jessie O. Samaniego; Norman D. S. Mendoza; Charles Darwin T. Racadio; Cris Reven L. Gibaga; Alexandria M. Tanciongco; Rico Neil M. Quierrez; Fern Rose A. Peregrino; Rachelle Clien G. Reyes; John Henry C. Gervasio (Isotopes in Environmental and Health Studies, 2026)

The influence of temperature and conductivity on metabolism and Per- and Polyfluoroalkyl Substance (PFAS) bioconcentration in Bluegill (Lepomis macrochirus) - Neil Fuller; Krista Kraskura; Sarah Hrynko; Michael K. Chanov; Jamie G. Suski; Youn J. Choi; Linda S. Lee; Christopher J. Salice (Ecotoxicology, 2026)
Aquatic organisms may be exposed to multiple concurrent stressors, including anthropogenic contaminants and alterations to abiotic parameters such as temperature and conductivity. Amid global climate change, elucidating the interactions between chemical and environmental factors is a priority. In recent years, per- and polyfluoroalkyl substances (PFAS) have emerged as contaminants of global concern owing to their persistence, bioaccumulation potential, and toxicity. While limited studies have documented the influence of temperature and conductivity on PFAS bioaccumulation in fish, the underlying physiological drivers associated with changes to uptake and elimination remain poorly understood. Therefore, the present study aimed to determine the influence of temperature and conductivity on metabolic parameters and bioconcentration of an environmentally relevant PFAS mixture in bluegill, Lepomis macrochirus . Fish were exposed to a mixture of perfluorooctane sulfonate (PFOS), perfluorohexane sulfonate (PFHxS), perfluorooctanoic acid (PFOA), and perfluorohexanoic acid (PFHxA) at 20 and 25 °C and conductivity levels of 300, 600, and 1200 µS/cm for a 32-day uptake and 32-day depuration period. Additionally, we measured individual resting metabolic rate (RMR), maximum metabolic rate (MMR), and aerobic scope under the same temperature and conductivity conditions. Overall, PFOS and PFHxS accumulation in the liver were consistently higher in fish at 20 °C compared to 25 °C, which was linked to more rapid contaminant elimination at higher temperatures. Resting and maximum metabolic rates increased with temperature, independent of conductivity. These results will facilitate the development of robust bioaccumulation models to enhance predictive modeling of PFAS accumulation and aid in understanding the physiological drivers of fish contaminant accumulation.

Crevice corrosion of CuNi 90/10 under simulated macrofouling in temperate and tropical Australian marine environments - M. A. Javed; R. Piola; W. C. Neil; S. A. Wade (Biofouling, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Corrigendum to “Isotope effects (Cl, O, C) of heterogeneous electrochemistry induced by Martian dust activities” [Earth and Planetary Science Letters 676 (2026) 119784] - Neil C. Sturchio; Hao Yan; Alian Wang; W. Andrew Jackson; Huiming Bao; Chuck Y.C. Yan; Linnea J. Heraty; Yu Wei; Quincy H.K. Qu; Kevin S. Olsen (Earth and Planetary Science Letters, 2026)

Nanopore sequencing for microbiological diagnosis of bacterial pneumonia: A systematic review and meta-analysis - Dianne Jaula Cunanan; Timothy Hudson David Culasino Carandang; John David Pilapil; Donmig Jaula Cunanan; Andrea Gail Mollasgo; Gerald Neil S. Manalo; Gail S. Co; Jason Rosch; Karen Carroll; Kin Israel Notarte (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Success of restoration strategies in preventing extirpation of 2 critically endangered coral species - Erinn M. Muller; Mark C. Ladd; Richard Karp; Phanor H. Montoya‐Maya; Ilsa B. Kuffner; Andrew C. Baker; Erich Bartels; Amanda Bourque; Abigail S. Clark; Nikkie Cox; Martine D'Alessandro; Ben Daughtry; et al. (Conservation Biology, 2026)
An unprecedented marine heatwave in 2023 caused widespread coral bleaching and mortality throughout the Caribbean. In the Florida Keys (USA), 2 foundation species, elkhorn coral ( Acropora palmata ) and staghorn coral ( Acropora cervicornis ), were severely affected. These species have been the primary focus of reef restoration in Florida for decades. Substantial losses of these species occurred in outplanted populations, in ocean‐based nurseries, and among remnant wild colonies, leading to uncertainty over their future in the Florida Keys, given recent observed trends in climate conditions. However, the past 2 decades of restoration activity created a community of experts, a network of ocean‐based and land‐based coral‐rearing infrastructure, and 2 independent land‐based coral gene banks that prevented regional extirpation and preserved much of the genetic richness of these critically endangered coral species. Without the past decades of effort and the emergency response associated with the 2023 bleaching event, Florida acroporids would largely have been lost. This outcome afforded by the restoration network in Florida demonstrates the value of proactively establishing resources prior to major disturbances. We identified several critical strategies that, in the context of existing climate change, are preventing the extirpation of coral species in Florida, including extending collaborative restoration efforts to solidify a network of trained experts; establishing trust‐focused relationships among management agencies and restoration groups; testing direct interventions to reduce light and temperature stress early during thermal anomalies; developing redundant ocean‐based and land‐based nurseries; and establishing living coral gene banks prior to major threats to prevent the extirpation of coral species.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Isotope effects (Cl, O, C) of heterogeneous electrochemistry induced by Martian dust activities - Neil C. Sturchio; Hao Yan; Alian Wang; W. Andrew Jackson; Huiming Bao; Chuck Y.C. Yan; Linnea J. Heraty; Yu Wei; Quincy H.K. Qu; Kevin S. Olsen (Earth and Planetary Science Letters, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

An atlas of ancient vegetation-induced sedimentary structures (VISS): Their biogeomorphological, sedimentological and evolutionary significance - James A. Craig; Neil S. Davies; William J. McMahon (Earth-Science Reviews, 2026)

Restoring the wild east: Predicting public support for cougar and red wolf reintroduction in the eastern United States - Benjamin Ghasemi; Jeremy T. Bruskotter; John A. Vucetich; L. Mark Elbroch; Robyn S. Wilson; Neil H. Carter; Axel Moehrenschlager; Shelby Perry; Joseph W. Hinton (Biological Conservation, 2026)

Warm Edge Kelp Populations Show Elevated Volatility to Marine Heatwaves - Jiaxin Shi; Scott Bennett; Jules B. Kajtar; Thomas Wernberg; Neville S. Barrett; Graham J. Edgar; Neil J. Holbrook (Ecology Letters, 2026)
Reliable predictions of species responses to intensifying temperature extremes are crucial for managing climate change impacts. However, limited data of species' responses to heat stress across their distribution restricts prediction accuracy. Here we analyse three‐decades of kelp abundance observations in Australia, including cool to warm‐edge populations, relative to marine heatwaves (MHWs). As MHWs intensified, changes in kelp abundances shifted from positive to negative. Warm‐edge populations displayed steeper declines in abundance change than central and cool‐edge populations under comparable MHWs. Our results support a hybrid thermal performance model, whereby thermal limits differ between populations, but performance volatility increases toward species' warm‐edge, heightening vulnerability of warm‐edge populations. Importantly, realised impacts of MHWs were evident at smaller thermal anomalies than predicted by experiments and distribution models, highlighting the importance of calibrating theoretical approaches with realised ecological change. By integrating a multi‐faceted approach, our study is generalisable for improving predictions of species' population vulnerability.

Direct measurement of mavacamten and deoxyATP perturbation of the SRX/DRX ratio in porcine cardiac myofibrils using a simple, accessible and multiplexed approach - Matvey Pilagov; Ateeqa Naim; Kenneth S. Campbell; Thomas Kampourakis; Michael A. Geeves; Neil M. Kad (Journal of Muscle Research and Cell Motility, 2025)
Cardiac muscle adapts to varying physiological demands by modulating the number of active myosin II motors available for contraction. These motors are organized into thick filaments in the sarcomere and generate force through an ATP-dependent interaction with thin filaments that contain actin. To conserve energy, when demand is low myosin can occupy the super-relaxed (SRX) state, which acts as a reserve. Here, we build upon the earlier studies to quantify the size of this cardiac reserve using fluorescence imaging of Cy3-ATP directly in myofibrils. This approach employs a pulse-chase method and exploits the high permeability of isolated myofibrils to monitor nucleotide release in situ. By preserving sarcomeric architecture while enabling rapid reagent exchange, this method bridges the gap between complex single-molecule imaging and traditional stopped-flow bulk assays using MANT-ATP. Using this approach we have studied biochemical perturbation of the SRX reserve with deoxyATP and mavacamten. DeoxyATP caused large depletion of the cardiac reserve, and mavacamten increased its size, consistent with its clinical application. Our results demonstrate the utility of this technique and the potential for further enhancement using multiplexing (i.e. imaging multiple samples in the same acquisition period), holding promise for future applications in health and disease.

Operational optimization of bipolar membrane electrodialysis for acid and base production in zero liquid discharge of high-salinity brine - Abdiel Lugo; Mohammed Fuwad Ahmed; Tayia L. Oddonetto; Punhasa S. Senanayake; Isuru Basnayake; Zachary Stoll; Masoume Ehsani; Neil E. Moe; John Barber; Huiyao Wang; Pei Xu (Desalination, 2025)

Opportunities in multiscale modeling of mosquito-borne flaviviruses - Carolin Zitzmann; Neil Alvin B. Adia; Priya S. Shah; Carrie Manore (BioSystems, 2025)

First insights into the fine-scale vertical movements of a Carolina hammerhead, Sphyrna gilberti, and a hybrid between Carolina and scalloped hammerhead - Lauren Horstmyer; Kirsty Ballard; Toby Daly-Engel; Kieran Stein; Eric Hoffmayer; Neil Hammerschlag; Bryan S. Frazier; Brooke Anderson; Beckah Campbell; James Sulikowski (Frontiers in Marine Science, 2025)
Satellite telemetry has enabled the tracking of marine predators’ vertical and horizontal habitat use and migration patterns. These insights provide valuable information that inform management and conservation of threatened species. In this study, a scalloped hammerhead, Sphyrna lewini, (125 cm FL; immature female) a Carolina hammerhead, Sphyrna gilberti, (138 cm FL; immature female) and a scalloped/Carolina hammerhead hybrid (160 cm FL; immature male) were tagged with PSATLIFE’s off the coast of North Carolina. Tag data revealed that the Carolina hammerhead exploited a wide depth range, with a maximum depth of 846 m. Dive patterns of the scalloped hammerhead revealed differences in vertical space use, with the scalloped hammerhead primarily remaining within the top 200 m of the water column, and with a maximum depth of 380 m. The hybrid individual demonstrated similar dive patterns to those of the scalloped hammerhead, with a maximum depth of 203 m. This study presents the first vertical movement data for Carolina and hybrid scalloped/Carolina hammerheads, offering new insights into interspecific variation in depth use. Future research should explore if there are differences in habitat use and foraging strategies, as they may serve as distinguishing characteristics and support the development of effective management measures.

Stacking and Intersecting Nitrogen 4Rs on Potato: Economic Analysis - Samuel H. Stapley; Christopher S. McIntosh; Matt A. Yost; Neil C. Hansen; Ryan C. Christensen; Bryan G. Hopkins (American Journal of Potato Research, 2025)
The 4Rs of nutrient management is an initiative to balance economics with sustainability. The objective was to evaluate individual and stacked 4R practices on potato ( Solanum tuberosum L.) profitability. Treatments included all combinations of two nitrogen (N) sources (urea or polymer coated urea [PCU]), two rates (82 or 100%), and/or two timing/placements (at emergence or split-applied). Gross income and net profit were determined using yields, market sale data, and costs. Total gross income was greatest for PCU split applied and PCU at emergence in 2020 and 2023, respectively. Gross income and net profit were higher for the full rate for PCU compared to urea. The detrimental effect of the reduced rate disappeared with PCU, but not urea. A reduced rate of PCU was similar to a full rate of split applied urea. These data suggest that PCU is a profitable N source for potato even at reduced rates.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Status of Florida’s pillar coral population: in situ declines and ex situ successes - Karen L. Neely; Rachel M. Morgan; Keri L. O’Neil; Nikkie Cox; David S. Gilliam; Michelle B. Mair; Brian K. Walker; Amanda Zummo; Cailin Harrell; Ananda Ellis (Frontiers in Marine Science, 2025)
The population of pillar coral, Dendrogyra cylindrus , in Florida was decimated from 2013 to 2020, primarily by the emergence of stony coral tissue loss disease (SCTLD). Monitoring of survivors from 2021 to early 2025 showed that the population underwent an additional 96% decline in live tissue, a 78% loss in living colonies, and a 55% loss of genotypes. SCTLD continued to be the primary cause of these losses. Although some surviving tissue isolates exhibited small amounts of growth, the population remains extremely small, with only an estimated 9.6 m 2 of tissue remaining on 23 colonies (15 genotypes). Additionally, the colonies are far too dispersed to successfully fertilize spawned gametes. Further declines in the population since 2020 highlight the instability of the remnant population and underscore the value of the pillar coral rescue program and ongoing propagation efforts. As of February 2025, eight different in situ and ex situ facilities were caring for rescued D. cylindrus . Experimental fragmentation at one in situ nursery identified variable, but continually improving, growth rates across multiple fragmentation events. Sexual propagation efforts at an ex situ nursery documented 105 different rescue fragments spawning over 5 years. The smallest fragment was 9 cm × 7 cm × 9 cm, suggesting a potential “minimum colony size” for this species to have reproductive capacity. During these spawning events, 82 juveniles were being raised ex situ in early 2025. Two of these sexually propagated juveniles spawned 6 years after settlement, thus establishing a potential minimum age for reproduction.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

2.4–2.3 Ga granitoids of the Arrowsmith orogeny, southwestern Rae craton, Canada: Syn- and post-orogenic magmatism during a global tectono-magmatic lull - Benjamin J.C. Neil; Thomas Chacko; Larry M. Heaman; S. Andy Dufrane; Robert A. Creaser; Edith Martel; Rebecca Canam; D. Graham Pearson (Precambrian Research, 2025)

Speciation of cesium in a radiocesium-bearing microparticle emitted from Unit 1 during the Fukushima nuclear accident by XANES spectroscopy using transition edge sensor - Yoshio Takahashi; Hikaru Miura; Shinya Yamada; Oki Sekizawa; Kiyofumi Nitta; Tadashi Hashimoto; Takumi Yomogida; Akiko Yamaguchi; Shinji Okada; Takaaki Itai; Hiroki Suga; Teruhiko Kashiwabara; et al. (Journal of Hazardous Materials, 2025)

Unvegetated rivers no longer exist: Plant-landscape interactions in the Mojave and Amargosa rivers, SW USA - Hamilton A. Allport; Neil S. Davies (Geomorphology, 2025)

A 12,000-year dinoflagellate cyst record on the Vancouver Island margin, Canada: tracing past climatic, primary productivity and oceanographic conditions - Zhen Li; Vera Pospelova; Kenneth Neil Mertens; Alice S. Chang; Yongsheng Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Setting the limit: cold rather than hot temperatures limit intertidal distribution of a coastal foundation species - Kerstin Wasson; Kim Cressman; Kathryn Beheshti; Erin C. Herder; Charlie Endris; Christopher D.G. Harley; Alicia Abadía-Cardoso; Rodrigo Beas-Luna; Joachim Carolsfeld; Andrew L. Chang; Jeffrey A. Crooks; Matthew C. Ferner; et al. (Marine Environmental Research, 2025)

Climate change threatens the sustainability of current timber harvesting practices across a latitudinal gradient in Siberia - Eric J. Gustafson; Melissa S. Lucash; Anatoly Z. Shvidenko; Brian R. Sturtevant; Dmitry Schepaschenko; Colin Mast; Neil Williams (European Journal of Forest Research, 2025)

Public engagement in climate assessment: lessons and opportunities - Allyza R. Lustig; Aaron Grade; Zena N. Grecni; Jeremy S. Hoffman; Neil Matouka; Danielle Meeker; Rachael Novak; Adam Parris; Allison Crimmins (Climatic Change, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Compressibility and permeability of flocculated microalgal sediment in filtration-permeation - Jincheng Wu; Neil Cagney; Gerald H. Meeten; Timothy G.J. Jones; Edo S. Boek (Journal of Water Process Engineering, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Enhancing the efficiency of electrodialysis brine concentrator to reduce the levelized cost of salt production through dynamic model-based simulations - Punhasa S. Senanayake; Mohammed Fuwad Ahmed; Abdiel Lugo; Zachary Stoll; Neil E. Moe; Masoume Ehsani; John Barber; Pei Xu; Huiyao Wang (Desalination, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Thickness of the stratigraphic record of Britain: How the fidelity of geological and fossil data is unrelated to rock quantity - James A. Craig; Ralph J. Battle; Yorick P. Veenma; William J. McMahon; Ben J. Slater; Anthony P. Shillito; Neil S. Davies (Earth-Science Reviews, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Demonstrating a biobased concept for the production of sustainable bacterial cellulose from mixed textile, agricultural and municipal wastes - Alexandra Lanot; Shivam Tiwari; Philip Purnell; Abdalla M. Omar; Miriam Ribul; Daniel J. Upton; Heather Eastmond; Ishrat J. Badruddin; Hannah F. Walker; Angharad Gatenby; Sharon Baurley; Paulo J.D.S. Bartolo; et al. (Journal of Cleaner Production, 2025)

In-utero exposure to real-life environmental chemicals disrupts gene expression within the hypothalamo-pituitary-gonadal axis of prepubertal and adult rams - Mohammad Ghasemzadeh Hasankolaei; Neil P. Evans; Chris S. Elcombe; Richard G. Lea; Kevin D. Sinclair; Vasantha Padmanabhan; Michelle Bellingham (Environmental Research, 2025)

Incidence and effects of anomalies and hybridization on Alabama freshwater fish index of biotic integrity results - Justin C. Bagley; Alicia K. Phillips; Sarah Buchanon; Patrick E. O’Neil; Elizabeth S. Huff (Environmental Monitoring and Assessment, 2024)

A multi-stage feature selection method to improve classification of potential super-agers and cognitive decliners using structural brain MRI data—a UK biobank study - Parvin Mohammadiarvejeh; Mohammad Fili; Alice Dawson; Brandon S. Klinedinst; Qian Wang; Shannin Moody; Neil Barnett; Amy Pollpeter; Brittany Larsen; Tianqi Li; Sara A. Willette; Jonathan P. Mochel; et al. (GeroScience, 2024)
Cognitive aging is described as the age-related decline in areas such as memory, executive function, reasoning, and processing speed. Super-Agers, adults over 80 years old, have cognitive function performance comparable to middle-aged adults. To improve cognitive reserve and potentially decrease Alzheimer’s disease (AD) risk, it is essential to contrast changes in regional brain volumes between “Positive-Agers” who have superior cognitive performance compared to their age peers but are not 80 years old yet and aging adults who show cognitive decline (i.e., “Cognitive Decliners”). Using longitudinal cognitive tests over 7–9 years in UK Biobank, principal component analysis (PCA) was first applied to four cognitive domains to create a general cognition (GC) composite score. The GC score was then used to identify latent cognitive groups. Given cognitive groups as the target variable and structural magnetic resonance imaging (sMRI) data and demographics as predictors, we developed a multi-stage feature selection algorithm to identify the most important features. We then trained a Random Forest (RF) classifier on the final set of 54 selected sMRI and covariate predictors to distinguish between Positive-Agers and Cognitive Decliners. The RF model achieved an AUC of 73%. The top 6 features were age, education, brain total surface area, the area of pars orbitalis, mean intensity of the thalamus, and superior frontal gyrus surface area. Prediction of cognitive trajectory types using sMRI may improve our understanding of successful cognitive aging.

Removing institutional barriers to long-term fieldwork is critical for advancing ecology - Kasim Rafiq; Neil R. Jordan; J. Weldon McNutt; John Neelo; Nina Attias; Dee Boersma; Meredith S. Palmer; Jennifer Ruesink; Briana Abrahms (Trends in Ecology & Evolution, 2024)

Ammonites as paleothermometers: Isotopically reconstructed temperatures of the Western Interior Seaway track global records - Jessie R.C. McCraw; Thomas S. Tobin; J. Kirk Cochran; Neil H. Landman (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The 2020 Mw 6.6 Vernadsky transform earthquake sequence: rupture and Coulomb stress changes surrounding an oceanic core complex - Guilherme W. S. de Melo; Neil C. Mitchell; Sergey Y. Sokolov (Marine Geophysical Research, 2024)
Oceanic core complexes (OCCs) are upwards-convex areas of outcropping lower crustal or upper mantle rocks raised to the seabed by normal faults, commonly associated with weak lithologies such as serpentinites. They are common adjacent to transform valleys of slow-spreading ridges. In this paper, we analyse the September 2020, Mw 6.6 strike-slip earthquake and its two-week long aftershock sequence within the Vernadsky transform valley, using recordings from regional seismic stations. The aftershocks occurred in two phases. During the first four days, ∼ 131 events occurred east and northeast of the mainshock, overlapping an adjacent OCC complex along the northern flank of the transform valley. During the following nine days, 20 aftershocks occurred, including a Mw 5.8 event close to the OCC. To refine the locations of aftershocks, the spatial spread of the events (clustering) was refined by double-difference relocating 114 events, and five with teleseismic relative relocation. Modeling of static Coulomb stresses was carried out, based on a mainshock rupture length compatible with the 26–30 km horizontal extent of aftershocks. This revealed that the aftershocks occurred mainly in areas where static Coulomb stresses decreased, not increased. Other researchers have suggested that changes in fault strength can arise from dynamic stresses during major earthquakes, leading to seismicity in areas of decreased Coulomb stress. We explore this idea in the context of OCCs.

One-Stop-Shop Cancer Screening Clinic: Acceptability Testing - Jeannie M. Au; Jamilia R. Sly; Leah C. Savage; Matthew Beyrouty; Neil S. Calman; Michaela Frazier; Jay Musella; Francesca Minardi; Lina H. Jandorf; Ellerie Weber; Saborny Mahmud; Sarah J. Miller (Journal of Cancer Education, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

PFAS distribution in cascade derived foam at wastewater treatment plants: The role of non-linear drainage, collapse induced enrichment, and implications for removal - Ethan S. Coffin; Donald M. Reeves; Daniel P. Cassidy; Neil D. Danielson; Mark A. Henry (Journal of Hazardous Materials, 2024)

Authenticating genuine Kakadu plum (Terminalia ferdinandiana) powders from fakes using stable isotope analysis and elemental profiling - Mariel Keaney; Debashish Mazumder; Carol V. Tadros; Jagoda Crawford; Patricia S. Gadd; Paul Saeki; Jesmond Sammut; Neil Saintilan (Food Control, 2024)

Life-cycle analysis of offshore macroalgae production systems in the United States - Hoyoung Kwon; Troy R. Hawkins; George G. Zaimes; Javier Infante; Hauke L. Kite-Powell; Michael S. Stekoll; Loretta Roberson; Beth Zotter; Simona Augyte; Greg Rocheleau; Neil Sims (Algal Research, 2024)

A multispecies hierarchical model to integrate count and distance‐sampling data - Neil A. Gilbert; Caroline M. Blommel; Matthew T. Farr; David S. Green; Kay E. Holekamp; Elise F. Zipkin (Ecology, 2024)
Integrated community models—an emerging framework in which multiple data sources for multiple species are analyzed simultaneously—offer opportunities to expand inferences beyond the single‐species and single‐data‐source approaches common in ecology. We developed a novel integrated community model that combines distance sampling and single‐visit count data; within the model, information is shared among data sources (via a joint likelihood) and species (via a random‐effects structure) to estimate abundance patterns across a community. Parameters relating to abundance are shared between data sources, and the model can specify either shared or separate observation processes for each data source. Simulations demonstrated that the model provided unbiased estimates of abundance and detection parameters even when detection probabilities varied between the data types. The integrated community model also provided more accurate and more precise parameter estimates than alternative single‐species and single‐data‐source models in many instances. We applied the model to a community of 11 herbivore species in the Masai Mara National Reserve, Kenya, and found considerable interspecific variation in response to local wildlife management practices: Five species showed higher abundances in a region with passive conservation enforcement (median across species: 4.5× higher), three species showed higher abundances in a region with active conservation enforcement (median: 3.9× higher), and the remaining three species showed no abundance differences between the two regions. Furthermore, the community average of abundance was slightly higher in the region with active conservation enforcement but not definitively so (posterior mean: higher by 0.20 animals; 95% credible interval: 1.43 fewer animals, 1.86 more animals). Our integrated community modeling framework has the potential to expand the scope of inference over space, time, and levels of biological organization, but practitioners should carefully evaluate whether model assumptions are met in their systems and whether data integration is valuable for their applications.

Incorporating geographic interdependencies into the resilience assessment of multimodal public transport networks - Georgia Boura; Neil S. Ferguson (Journal of Transport Geography, 2024)

Interactions between vegetation and river morphodynamics. Part I: Research clarifications and challenges - Dov Corenblit; Hervé Piégay; Florent Arrignon; Eduardo González-Sargas; Anne Bonis; Neil S. Davies; Dav M. Ebengo; Virginia Garófano-Gómez; Angela M. Gurnell; Annie L. Henry; Borbála Hortobágyi; Francisco Martínez-Capel; et al. (Earth-Science Reviews, 2024)

Predictions & perceptions: A social-ecological analysis of human-carnivore conflict in Botswana - Dylan E. Feldmeier; Oswald J. Schmitz; Neil H. Carter; Gaseitsiwe S. Masunga; Kaggie D. Orrick (Biological Conservation, 2024)

Passive Removal of Mn from Mine Water Using Oxic Aggregate Beds: Results of Two Pilot Systems - Robert S. Hedin; Neil Wolfe; Benjamin Hedin (Mine Water and the Environment, 2024)

A quasi-geostrophic analysis of summertime southern African linear-regime westerly waves - Thando Ndarana; Tsholanang S. Rammopo; Mary-Jane M. Bopape; Neil C. G. Hart; Chris J. C. Reason; Hector Chikoore (Climate Dynamics, 2024)
Linear-regime westerly waves that propagate across the South African domain are often linked to well-known rainfall producing systems such as tropical temperate troughs and synoptic scale tropical low-pressure systems, and ridging South Atlantic Ocean anticyclones at the surface. It is accepted that the baroclinic waves that propagate across the domain provide the lifting mechanism that causes the required vertical motion for rainfall to occur. This study shows that there exists a jet streak embedded in these waves that is located downstream of the trough axis, to the east of which vertically upward motion is expected to occur. The entrance of the jet streak passes just south of the country, as the waves propagate past the domain. The study further shows that for this class of waves, the vertical motion that causes rainfall to occur is induced by the thermally direct transverse ageostrophic circulation that is located at this jet entrance. This is instead of the conventional upper air divergence that is located at the inflection point east of the trough axis. Using a method of decomposing the Q -vector into its transverse ( $${Q}_n$$ Q n ) and shear ( $${Q}_s$$ Q s ) components, the divergence fields of which are used to decompose the vertical motion into the corresponding components, i.e $$ω _n$$ ω n and $$ω _s$$ ω s , respectively; it was shown that the vertical motion over South Africa is explained more by the former than the latter. Therefore, the uplift over the country and that located at the infection point east of the trough are dynamically distinct processes. Taking the limitations of the quasi-geostrophic framework into consideration, the study concludes that during the passage of linear-regime waves vertical motion that might lead to rainfall is caused by the circulation at the jet entrance and not the divergence in the baroclinic wave.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Carbonate deformation through the brittle-ductile transition: The case of the SW Helvetic nappes, Switzerland - Giovanni Luca Cardello; Stefano M. Bernasconi; Maria Giuditta Fellin; Meinert Rahn; Ricarda Rosskopf; Colin Maden; Neil S. Mancktelow (Journal of Structural Geology, 2024)

Conservation genomics of the threatened Trispot Darter (Etheostoma trisella) - Kayla M. Fast; Brook L. Fluker; Bernard R. Kuhajda; Patrick E. O’Neil; Stuart W. McGregor; Matthew S. Piteo; Michael W. Sandel (Conservation Genetics, 2024)

Rethinking atoll futures: local resilience to global challenges - Sebastian Steibl; Paul S. Kench; Hillary S. Young; Alex S. Wegmann; Nick D. Holmes; Nancy Bunbury; Teurumereariki Hinano Teavai-Murphy; Neil Davies; Frank Murphy; James C. Russell (Trends in Ecology & Evolution, 2024)

Mapping the cellular landscape of Atlantic salmon head kidney by single cell and single nucleus transcriptomics - Adriana M.S. Andresen; Richard S. Taylor; Unni Grimholt; Rose Ruiz Daniels; Jianxuan Sun; Ross Dobie; Neil C. Henderson; Samuel A.M. Martin; Daniel J. Macqueen; Johanna H. Fosse (Fish & Shellfish Immunology, 2024)

Invasion of farmland hedgerows by non-native small mammals is associated with lower soil surface invertebrate diversity, abundance, body size and biomass - W. Ian Montgomery; Sally S. J. Montgomery; James O’Neill; Neil Reid (Biological Invasions, 2024)
Small mammals in farmland hedgerows feed on soil surface invertebrates with non-native invasive species potentially affecting prey species and populations. We investigated terrestrial invertebrates using pitfall traps and leaf litter samples across four zones of invasion in Ireland: (1) native species only (wood mouse Apodemus sylvaticus and pygmy shrew Sorex minutus ), (2) natives plus the non-native bank vole ( Myodes glareolus ), (3) natives plus the non-native greater white-toothed shrew ( Crocidura russula ) and (4) natives plus both. After accounting for regional and local environmental variation, small mammal invasion was associated with lower invertebrate species richness (9–39% lower than uninvaded zones), reduced abundance (18–56% lower), shorter arthropod body length (24–52% shorter) and lower arthropod biomass (63–89% lower). Negative effects were observed on a wide range of disparate functional groups spanning phytophagous, detritivorus, zoophagous and omnivorous taxa including: the Staphylinidae, Carabidae and Coleoptera larvae, Isopoda, Diplopoda, Diptera, Hymenoptera, Pulmonata and Acari. The greater white-toothed shrew had greater negative effects than the bank vole with presence of both having greater effects than either alone though the majority of their combined effects were largely attributable to the former. The bank vole may mitigate some of the negative effects of the greater white-toothed shrew on invertebrate abundance perhaps indicating of some form of trophic interaction. Predation of detritivores and large invertebrate predators may impact farmland ecosystem service delivery i.e. nutrient cycling and pest biocontrol. Hedgerow biodiversity loss may induce indirect trophic cascades negatively impacting other taxa including farmland birds.

Host population crashes disrupt the diversity of associated marine microbiomes - William S. Pearman; Sergio E. Morales; Felix Vaux; Neil J. Gemmell; Ceridwen I. Fraser (Environmental Microbiology, 2024)
Host‐associated microbial communities are shaped by myriad factors ranging from host conditions, environmental conditions and other microbes. Disentangling the ecological impact of each of these factors can be particularly difficult as many variables are correlated. Here, we leveraged earthquake‐induced changes in host population structure to assess the influence of population crashes on marine microbial ecosystems. A large (7.8 magnitude) earthquake in New Zealand in 2016 led to widespread coastal uplift of up to ~6 m, sufficient to locally extirpate some intertidal southern bull kelp populations. These uplifted populations are slowly recovering, but remain at much lower densities than at nearby, less‐uplifted sites. By comparing the microbial communities of the hosts from disturbed and relatively undisturbed populations using 16S rRNA gene amplicon sequencing, we observed that disturbed host populations supported higher functional, taxonomic and phylogenetic microbial beta diversity than non‐disturbed host populations. Our findings shed light on microbiome ecological assembly processes, particularly highlighting that large‐scale disturbances that affect host populations can dramatically influence microbiome structure. We suggest that disturbance‐induced changes in host density limit the dispersal opportunities of microbes, with host community connectivity declining with the density of host populations.

Assessment of gill microbiome of two strains of Atlantic salmon reared in flowthrough and recirculation hatcheries and following seawater transfer - Petra R. Quezada-Rodriguez; Jamie Downes; Fintan Egan; Richard S. Taylor; Samantha White; Aisling Brenan; Megan L. Rigby; Barbara F. Nowak; James W. Wynne; Neil M. Ruane (Aquaculture, 2024)

Inter-colony variation in predation, mercury burden and adult survival in a declining seabird - Anna M. Calvert; Sarah E. Gutowsky; David A. Fifield; Neil M. Burgess; Rachel Bryant; Gail S. Fraser; Carina Gjerdrum; April Hedd; Patricia L. Jones; Robert A. Mauck; Laura McFarlane Tranquilla; William A. Montevecchi; et al. (Science of The Total Environment, 2024)

Cross-adaptation from heat stress to hypoxia: A systematic review and exploratory meta-analysis - Ashley G.B. Willmott; Alicia G. Diment; Henry C. Chung; Carl A. James; Neil S. Maxwell; Justin D. Roberts; Oliver R. Gibson (Journal of Thermal Biology, 2024)

Cell atlas of the Atlantic salmon spleen reveals immune cell heterogeneity and cell-specific responses to bacterial infection - Jianxuan Sun; Rose Ruiz Daniels; Adam Balic; Adriana M.S. Andresen; Håvard Bjørgen; Ross Dobie; Neil C. Henderson; Erling Olaf Koppang; Samuel A.M. Martin; Johanna Hol Fosse; Richard S. Taylor; Daniel J. Macqueen (Fish & Shellfish Immunology, 2024)

A Genome Wide Association Study (GWAS) Identifies SNPs Associated with Resistance to Tobacco Rattle Virus (TRV) and Potato Mop-Top Virus (PMTV) in a Tetraploid Mapping Population of Potato - Noelle L. Anglin; Shashi K. R. Yellarreddygari; Neil C. Gudmestad; Vidyasagar Sathuvalli; Charles R. Brown; Max Feldman; Walter S. De Jong; David S. Douches; Richard G. Novy; Joseph J. Coombs (American Journal of Potato Research, 2024)

Tunnel valley formation beneath deglaciating mid-latitude ice sheets: Observations and modelling - James D. Kirkham; Kelly A. Hogan; Robert D. Larter; Neil S. Arnold; Jeremy C. Ely; Chris D. Clark; Ed Self; Ken Games; Mads Huuse; Margaret A. Stewart; Dag Ottesen; Julian A. Dowdeswell (Quaternary Science Reviews, 2024)

The infill of tunnel valleys in the central North Sea: Implications for sedimentary processes, geohazards, and ice-sheet dynamics - James D. Kirkham; Kelly A. Hogan; Robert D. Larter; Ed Self; Ken Games; Mads Huuse; Margaret A. Stewart; Dag Ottesen; Daniel P. Le Heron; Alex Lawrence; Ian Kane; Neil S. Arnold; et al. (Marine Geology, 2024)

Autoignition temperature trends for various chemical families - Mark E. Redd; Cassandra J. Guffey; Ethan L. Gustafson; Elizabeth H. Hart; Keturah S. McQuade; Neil F. Giles; Thomas A. Knotts IV; W. Vincent Wilding (Fuel, 2024)

Spawning induction for Latin American fishes - Alejandro S. Mechaly; Sergio R. Batlouni; Mariano Elisio; Eduardo A. Sanches; Jonathan Chacon Guzmán; Minerva Maldonado García; Adriana Rodríguez‐Forero; Paula Vissio; Elvira Fatsini; Jesús Núñez; Neil Duncan (Reviews in Aquaculture, 2024)
Aquaculture offers solutions to meet the growing global demand for fish, and reports from the UN‐FAO indicate that aquaculture production in Latin America (LA) has grown at rates above the world average in recent years. One of the major constraints in the diversification of LA aquaculture is the control of reproduction in several popular native fish species for which difficulties in captive propagation have not yet been sufficiently overcome. This article reviews the use of hormone treatments to promote reproduction in females of these native fish species. LA has played a key role in the history of development of hormone administration, including the first hormonally induced spawning. That contribution is included in a historical overview of the discovery of the major hormones used in fish culture. The review provides a summary of difficulties to propagate females of various native fishes and the effects of administering hormones to enhance reproduction. Induced spawning of certain freshwater species was mainly achieved with pituitary extracts or human chorionic gonadotropin (hCG), although gonadotropin‐releasing hormone analogues (GnRHa) treatments are being researched, and successful studies suggest that low doses may be more effective. Research on new and emerging aquaculture species has applied both gonadotropins (Gths) and GnRHa‐based treatments, and GnRHa treatments have shown potential for marine species. However, native marine species new to aquaculture have also been conditioned to spawn spontaneously without hormones. Finally, we proposed future lines of research to examine reproductive strategies and GnRHa‐based hormone treatments to improve reproductive control for economically important fish species of LA.

Science opportunities with solar sailing smallsats - Slava G. Turyshev; Darren Garber; Louis D. Friedman; Andreas M. Hein; Nathan Barnes; Konstantin Batygin; Michael E. Brown; Leroy Cronin; Artur R. Davoyan; Amber Dubill; T. Marshall Eubanks; Sarah Gibson; et al. (Planetary and Space Science, 2023)

Phytohormonal impacts on fatty acid profiles in Chlorella vulgaris Beijerinck: endogenous identification and exogenous application of cytokinins and abscisic acid - Kira Ramphal; Ainsely Lewis; Natasha A. Trzaskalski; Anna Kisiala; Erin N. Morrison; Suresh S. Narine; R. J. Neil Emery (Journal of Applied Phycology, 2023)

Defining optimal thresholds for digital Brix refractometry to determine IgG concentration in ewe colostrum and lamb serum in Scottish lowland sheep flocks - Kim Hamer; Michelle Bellingham; Neil P. Evans; Rheinallt O. Jones; Katharine S. Denholm (Preventive Veterinary Medicine, 2023)

Ichnology of a Middle Devonian regression: Environment, terrestrialization and true substrate controls on trace fossils of the Hangman Sandstone Formation, SW England - Neil S. Davies; William J. McMahon; Anthony P. Shillito; Yorick P. Veenma; James A. Craig (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Sexually dimorphic impact of preconceptional and gestational exposure to a real-life environmental chemical mixture (biosolids) on offspring growth dynamics and puberty in sheep - Neil P. Evans; Michelle Bellingham; Christopher S. Elcombe; Mohammad Ghasemzadeh-Hasankolaei; Richard G. Lea; Kevin D. Sinclair; Vasantha Padmanabhan (Environmental Toxicology and Pharmacology, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Nonlinear behaviour of corrosion damaged low-strength short reinforced concrete columns under compressive axial cyclic loading - Hammed O. Aminulai; Andrew F. Robinson; Neil S. Ferguson; Mohammed M. Kashani (Engineering Structures, 2023)

Characterisation of volatile organic compounds in hospital indoor air and exposure health risk determination - Thiphanie P. Riveron; Michael J. Wilde; Wadah Ibrahim; Liesl Carr; Paul S. Monks; Neil J. Greening; Erol A. Gaillard; Chris E. Brightling; Salman Siddiqui; Anna L. Hansell; Rebecca L. Cordell (Building and Environment, 2023)

Corrigendum to “A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa” [Biol. Conserv. 284 (2023) 110163] - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

A systematic conservation plan identifying critical areas for improved chondrichthyan protection in South Africa - Nina Faure-Beaulieu; Amanda T. Lombard; Jennifer Olbers; Victoria Goodall; Charlene da Silva; Ryan Daly; Gareth Jordaan; Sven E. Kerwath; Alison Kock; Bruce Q. Mann; Taryn S. Murray; Patricia Albano; et al. (Biological Conservation, 2023)

Biogeomorphology of Ireland's oldest fossil forest: Plant-sediment and plant-animal interactions recorded in the Late Devonian Harrylock Formation, Co. Wexford - Yorick P. Veenma; Neil S. Davies; Kenneth T. Higgs; William J. McMahon (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Developmental exposure to a real-life environmental chemical mixture alters testicular transcription factor expression in neonatal and pre-pubertal rams, with morphological changes persisting into adulthood - Chris S. Elcombe; Ana Monteiro; Mohammad Ghasemzadeh-Hasankolaei; Vasantha Padmanabhan; Richard Lea; Kevin D. Sinclair; Neil P. Evans; Michelle Bellingham (Environmental Toxicology and Pharmacology, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Visualizing Long-Term Forest Recovery After Management and Wildfire at Miller Creek Demonstration Forest - Neil G Williams; Justin S Crotteau; David K Wright; Adele Underwood; Peter F Stickney (Journal of Forestry, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Geothermal energy production adversely affects a sensitive indicator species within sagebrush ecosystems in western North America - Peter S. Coates; Brian G. Prochazka; Shawn T. O'Neil; Sarah C. Webster; Shawn Espinosa; Mark A. Ricca; Steven R. Mathews; Michael Casazza; David J. Delehanty (Biological Conservation, 2023)

Relationship between in feed drugs, antibiotics and organic enrichment in marine sediments at Canadian Atlantic salmon aquaculture sites - M.V. Kingsbury; D. Hamoutene; P. Kraska; A. Lacoursière-Roussel; F. Page; T. Coyle; T. Sutherland; O. Gibb; C.W. Mckindsey; F. Hartog; S. Neil; K. Chernoff; et al. (Marine Pollution Bulletin, 2023)

A Magnetohydrodynamic enhanced entry system for space transportation: MEESST - Andrea Lani; Vatsalya Sharma; Vincent F. Giangaspero; Stefaan Poedts; Alan Viladegut; Olivier Chazot; Jasmine Giacomelli; Johannes Oswald; Alexander Behnke; Adam S. Pagan; Georg Herdrich; Minkwan Kim; et al. (Journal of Space Safety Engineering, 2023)

Acoustic tracking of a threatened juvenile shark species, the smooth hammerhead (Sphyrna zygaena), reveals vulnerability to exploitation at the boundary of a marine reserve - Patricia S. Albano; Chris Fallows; Monique Fallows; Lacey H. Williams; Taryn Murray; Oliver Sedgwick; Neil Hammerschlag (Frontiers in Marine Science, 2023)
The coastal waters of South Africa are habitat to a diverse composition of sharks that are vulnerable to exploitation, many of which are endemic and/or classified by the International Union for Conservation of Nature (IUCN) Red List as Threatened or Data Deficient. Accordingly, this region has been identified as a global research and conservation priority for elasmobranchs. The De Hoop Marine Protected Area (MPA), in the Western Cape Province of South Africa, provides 288 km 2 of no-take protection within its boundaries. However, the region experiences heavy commercial fishing, with two vessels actively operating as dedicated shark longliners (as of 2022). When crossing MPA boundaries, sharks are susceptible to capture by these vessels. Utilizing passive acoustic telemetry, the present study evaluated the movements of a threatened juvenile shark species, the smooth hammerhead ( Sphyrna zygaena ), both inside and adjacent to the De Hoop MPA, and along the greater coastline. Movement data from 20 tagged sharks were used to explore the effects of spatial, environmental, and management variables on their residency and movement patterns. Results indicate a high reliance of sharks on unprotected waters immediately adjacent to the MPA’s eastern boundary, an area of high biological productivity due to its proximity to the mouth of an estuary. Although some tagged sharks did move regionally along the South African coastline, individuals spent 95% of their days detected just outside the eastern boundary of the MPA, rendering them vulnerable to commercial shark longlining occurring there. These findings have conservation implications for smooth hammerhead sharks in South Africa and present an opportunity to revisit management practices that may optimize spatial protection for an important life stage of this threatened species.

The colonization of drylands by early vascular plants: Evidence from Early Devonian fossil soils and in situ plant traces from South China - Jinzhuang Xue; Jiashu Wang; Pu Huang; Lu Liu; Tianzheng Huang; Lijun Zhang; Xianyan Wang; Bing Shen; Deming Wang; Jianbo Liu; Neil S. Davies; James F. Basinger (Earth-Science Reviews, 2023)

Climate processes and drivers in the Pacific and global warming: a review for informing Pacific planning agencies - Savin Chand; Scott Power; Kevin Walsh; Neil Holbrook; Kathleen McInnes; Kevin Tory; Hamish Ramsay; Ron Hoeke; Anthony S. Kiem (Climatic Change, 2023)
Pacific Island countries are vulnerable to climate variability and change. Developing strategies for adaptation and planning processes in the Pacific requires new knowledge and updated information on climate science. In this paper, we review key climatic processes and drivers that operate in the Pacific, how they may change in the future and what the impact of these changes might be. In particular, our emphasis is on the two major atmospheric circulation patterns, namely the Hadley and Walker circulations. We also examine climatic features such as the South Pacific Convergence Zone and Intertropical Convergence Zone, as well as factors that modulate natural climate variability on different timescales. It is anticipated that our review of the main climate processes and drivers that operate in the Pacific, as well as how these processes and drivers are likely to change in the future under anthropogenic global warming, can help relevant national agencies (such as Meteorological Services and National Disaster Management Offices) clearly communicate new information to sector-specific stakeholders and the wider community through awareness raising.

Climatic controls on the survival and loss of ancient types of barley on North Atlantic Islands - Peter Martin; Terence A. Brown; Timothy S. George; Björn Gunnarson; Neil J. Loader; Paul Ross; John Wishart; Rob Wilson (Climatic Change, 2023)
For ancient types of barley at sites in the Scottish Isles, Faroes, and Iceland, we calculated minimum temperature requirements for grain production (grain production threshold, GPT) as accumulated degree days over the cropping season. Site suitability for barley from AD 1200 to 2000 was investigated by comparing these thresholds with reconstructions of annual cropping season degree days (CSDD) using temperature and tree-ring data. In Iceland, between AD 1200 and 1500, reconstructed CSDD were more favorable in the southwest (Reykjavik), with fewer years below the GPT, than in the North, East and West, but there were two periods (1340–1389 and 1426–1475) with low average CSDD and several years below the GPT which possibly influenced the abandonment of barley cultivation around this time. Reconstructed CSDD for the Faroes (Tórshavn) had only one year below the GPT, but 15 periods of four or more consecutive years with low CSDD which would have challenged barley cultivation, especially in the thirteenth century. Reconstructed CSDD were highest for the Scottish Isles, allowing a more prominent role of barley in the farming system and economy. Nevertheless, years with poor harvests or famines were common and about half were associated with low CSDD, resulting in a significant temperature link but also demonstrating the important contribution of other factors. Despite frequent unfavorable years in both the Faroes and Scottish Isles, resilient production systems, well-adapted barley strains and socio-economic factors allowed barley cultivation to continue, and some ancient types to survive to the present day.

Experimental shake table validation of damping behaviour in inerter-based dampers - Predaricka Deastra; David J. Wagg; Neil D. Sims; Robin S. Mills (Bulletin of Earthquake Engineering, 2023)

Species portfolio effects dominate seasonal zooplankton stabilization within a large temperate lake - Reilly F. O'Connor; Bailey C. McMeans; Neil Rooney; Matthew M. Guzzo; Joelle D. Young; Kevin S. McCann (Ecology, 2023)
Portfolio effects (PEs) in ecology refer to the suite of phenomenon where the temporal variation of aggregate ecosystem properties (i.e., abundance) is lower than that of their ecosystem components. An example of this is where differential responses of species to environmental variation generate stability at higher levels of ecological organization (e.g., local community, metapopulation, metacommunity). Most of the research examining such PEs has focused on spatial or interannual variation of ecosystems; however, as global change continues to alter seasonality and ecosystem functioning, understanding the underlying food web structures that help maintain stability at multiple spatial and temporal scales is critical to managing ecological systems. Recent advances investigating diversity‐stability relationships has led to the development of frameworks that incorporate a metacommunity perspective which allows for the partitioning of PEs across organizational scales (i.e., local community, metapopulation, cross‐community, metacommunity) from local population dynamics (total). This partitioning yields insights into the mechanisms that generate observed PEs in nature. Here, we employed one of these recently developed frameworks on a temporally (1986–1999, 2008–2019) and spatially (five sampling stations, local communities) extensive data set of zooplankton abundance (e.g., density) within a large temperate lake to investigate how temporal (seasonal) and spatial (among site) PEs influence stability within the zooplankton metacommunity. We found that seasonal asynchrony of different zooplankton species within local communities and across communities generated the vast majority of stabilization, while spatial (i.e., metapopulation) dynamics were more synchronous and contributed little to overall system stability. Furthermore, significantly positive diversity‐asynchrony relationships at the total, local‐ and cross‐community scales were found as asynchrony was positively correlated with local Shannon diversity. Last, a comparison of PEs over the time periods, during which significant local and global changes (i.e., climate warming, invasive species) have occurred suggests that PEs may be eroding, as increasingly synchronous dynamics and declining diversity in recent years have led to a rise in metacommunity variability. We end by arguing for the critical importance of understanding seasonally driven stabilizing mechanisms as local and global changes threaten to fundamentally alter seasonal signals with potentially strong implications for the structures that lend stability to ecosystems.

‘Eye in the sky’: Off-the-shelf unmanned aerial vehicle (UAV) highlights exposure of marine turtles to floating litter (FML) in nearshore waters of Mayo Bay, Philippines - Neil Angelo S. Abreo; Remie M. Aurelio; Vladimer B. Kobayashi; Kirsten F. Thompson (Marine Pollution Bulletin, 2023)

A warmer environment can reduce sociability in an ectotherm - Natalie Pilakouta; Patrick J. O'Donnell; Amélie Crespel; Marie Levet; Marion Claireaux; Joseph L. Humble; Bjarni K. Kristjánsson; Skúli Skúlason; Jan Lindström; Neil B. Metcalfe; Shaun S. Killen; Kevin J. Parsons (Global Change Biology, 2023)
The costs and benefits of being social vary with environmental conditions, so individuals must weigh the balance between these trade‐offs in response to changes in the environment. Temperature is a salient environmental factor that may play a key role in altering the costs and benefits of sociality through its effects on food availability, predator abundance, and other ecological parameters. In ectotherms, changes in temperature also have direct effects on physiological traits linked to social behaviour, such as metabolic rate and locomotor performance. In light of climate change, it is therefore important to understand the potential effects of temperature on sociality. Here, we took the advantage of a ‘natural experiment’ of threespine sticklebacks from contrasting thermal environments in Iceland: geothermally warmed water bodies (warm habitats) and adjacent ambient‐temperature water bodies (cold habitats) that were either linked (sympatric) or physically distinct (allopatric). We first measured the sociability of wild‐caught adult fish from warm and cold habitats after acclimation to a low and a high temperature. At both acclimation temperatures, fish from the allopatric warm habitat were less social than those from the allopatric cold habitat, whereas fish from sympatric warm and cold habitats showed no differences in sociability. To determine whether differences in sociability between thermal habitats in the allopatric population were heritable, we used a common garden breeding design where individuals from the warm and the cold habitat were reared at a low or high temperature for two generations. We found that sociability was indeed heritable but also influenced by rearing temperature, suggesting that thermal conditions during early life can play an important role in influencing social behaviour in adulthood. By providing the first evidence for a causal effect of rearing temperature on social behaviour, our study provides novel insights into how a warming world may influence sociality in animal populations.

Habitat restoration weakens negative environmental effects on telomere dynamics - Darryl McLennan; Sonya K. Auer; Simon McKelvey; Lynn McKelvey; Graeme Anderson; Winnie Boner; Jessica S. Duprez; Neil B. Metcalfe (Molecular Ecology, 2022)
Habitat quality can have far‐reaching effects on organismal fitness, an issue of concern given the current scale of habitat degradation. Many temperate upland streams have reduced nutrient levels due to human activity. Nutrient restoration confers benefits in terms of invertebrate food availability and subsequent fish growth rates. Here we test whether these mitigation measures also affect the rate of cellular ageing of the fish, measured in terms of the telomeres that cap the ends of eukaryotic chromosomes. We equally distributed Atlantic salmon eggs from the same 30 focal families into 10 human‐impacted oligotrophic streams in northern Scotland. Nutrient levels in five of the streams were restored by simulating the deposition of a small number of adult Atlantic salmon Salmo salar carcasses at the end of the spawning period, while five reference streams were left as controls. Telomere lengths and expression of the telomerase reverse transcriptase (TERT) gene that may act to lengthen telomeres were then measured in the young fish when 15 months old. While TERT expression was unrelated to any of the measured variables, telomere lengths were shorter in salmon living at higher densities and in areas with a lower availability of the preferred substrate (cobbles and boulders). However, the adverse effects of these habitat features were much reduced in the streams receiving nutrients. These results suggest that adverse environmental pressures are weakened when nutrients are restored, presumably because the resulting increase in food supply reduces levels of both competition and stress.

Understanding the potential release of microplastics from coatings used on commercial ships - Mario N. Tamburri; Zhi Yang Soon; Christopher Scianni; Christer L. Øpstad; Neil S. Oxtoby; Simon Doran; Lisa A. Drake (Frontiers in Marine Science, 2022)
Microplastic pollution in the ocean is a critical, global environmental concern. Although believed to be a comparatively small contributor, the paints applied to commercial ships have been identified as a source of microplastics because polymers are used as binding agents in all anticorrosive and antifouling marine coatings. Furthermore, the release of microplastics from coatings may be amplified by in-water cleaning operations to remove biofouling. A comprehensive, detailed assessment and review of the array of commercial ships’ coatings, specifically characteristics, behavior, and fate over time, has not been conducted in the context of ocean microplastic pollution. This Policy Brief identifies gaps and proposes actions to better understand the fate of released particles with the goal to inform appropriate and effective solutions.

Optimum root zone temperature of photosynthesis and plant growth depends on air temperature in lettuce plants - Namiko Yamori; Christopher P. Levine; Neil S. Mattson; Wataru Yamori (Plant Molecular Biology, 2022)

Predicting an Athlete’s Physiological and Haematological Response to Live High-Train High Altitude Training Using a Hypoxic Sensitivity Test - Gareth Turner; Kate L. Spilsbury; David J. Green; Barry W. Fudge; Jamie S. M. Pringle; Alan J. Richardson; Neil S. Maxwell (Journal of Science in Sport and Exercise, 2022)

Prevalence of epitheliocystis in freshwater Atlantic salmon reared in flow‐through and recirculation aquaculture systems - Petra R. Quezada‐Rodriguez; Richard S. Taylor; Jamie Downes; Fintan Egan; Samantha White; Aisling Brenan; Megan Rigby; Barbara F. Nowak; Neil M. Ruane; James W. Wynne (Journal of Fish Diseases, 2022)
Epitheliocystis, an intracellular bacterial infection in the gills and skin epithelium, has been frequently reported in Atlantic salmon ( Salmo salar ) during freshwater production in a number of countries. This study describes the prevalence and intensity of a natural epitheliocystis infection present in the gills of two strains of Atlantic salmon reared in either a flow‐through (FT) or a recirculation aquaculture system (RAS) in Ireland. Repeated sampling of gills prior to and throughout seawater transfer, histology and quantitative real‐time PCR were used to determine infection prevalence and intensity. Despite no clinical gill disease, and minor histopathological changes, epitheliocystis lesions were identified in histology at all time points. Specific PCR confirmed the presence of Candidatus Clavichlamydia salmonicola in both strains and its number of copies was correlated with intensity of epitheliocystis lesions. A significant interaction between hatchery system and fish strain on the prevalence and intensity of gill epitheliocystis was found both using histological and molecular methods. Specifically, fish from FT had higher prevalence and intensity than RAS reared fish and within FT, the Irish cohort were more affected than Icelandic.

Coastal seascape variability in the intensifying East Australian Current Southern Extension - Lachlan R. Phillips; Neil Malan; Moninya Roughan; Robert Harcourt; Ian Jonsen; Martin Cox; Andrew S. Brierley; David Slip; Adam Wilkins; Gemma Carroll (Frontiers in Marine Science, 2022)
Coastal pelagic ecosystems are highly variable in space and time, with environmental conditions and the distribution of biomass being driven by complex processes operating at multiple scales. The emergent properties of these processes and their interactive effects result in complex and dynamic environmental mosaics referred to as “seascapes”. Mechanisms that link large-scale oceanographic processes and ecological variability in coastal environments remain poorly understood, despite their importance for predicting how ecosystems will respond to climate change. Here we assessed seascape variability along the path of the rapidly intensifying East Australian Current (EAC) Southern Extension in southeast Australia, a hotspot of ocean warming and ecosystem tropicalisation. Using satellite and in situ measures of temperature, salinity and current velocity coupled with contemporaneous measurements of pelagic biomass distribution from nine boat-based active acoustic surveys in five consecutive years, we investigated relationships between the physical environment and the distribution of pelagic biomass (zooplankton and fish) at multiple timescales. Survey periods were characterised by high variability in oceanographic conditions, with variation in coastal conditions influenced by meso-to-large scale processes occurring offshore, including the position and strength of eddies. Intra-annual variability was often of a similar or greater magnitude to inter-annual variability, suggesting highly dynamic conditions with important variation occurring at scales of days to weeks. Two seascape categories were identified being characterised by (A) warmer, less saline water and (B) cooler, more saline water, with the former indicating greater influence of the EAC on coastal processes. Warmer waters were also associated with fewer, deeper and less dense biological aggregations. As the EAC continues to warm and penetrate further south, it is likely that this will have substantial effects on biological activity in coastal pelagic ecosystems, including a potential reduction in the accessibility of prey aggregations to surface-feeding predators and to fisheries. These results highlight the import role of offshore oceanographic processes in driving coastal seascape variability and biological activity in a region undergoing rapid oceanic warming and ecological change.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

Age-Dependent Dispersal and Relatedness in Tiger Sharks (Galeocerdo cuvier) - Margaret A. McClain; Neil Hammerschlag; Austin J. Gallagher; J. Marcus Drymon; R. Dean Grubbs; Tristan L. Guttridge; Matthew J. Smukall; Bryan S. Frazier; Toby S. Daly-Engel (Frontiers in Marine Science, 2022)
Understanding dispersal in large marine fauna is necessary for conservation, but movement patterns often vary widely by sex and life stage. In sharks, genetic studies have shown evidence of widespread male-biased dispersal, though tagging and tracking studies on the same populations show both sexes using site fidelity, including philopatry, and moving similar distances. We used a suite of microsatellite loci and DNA samples from 362 previously-tagged tiger sharks (Galeocerdo cuvier) in the northwestern Atlantic, including a large number of residential juveniles, to evaluate reproductive dispersal in light of demographic and published tracking data. We found that lumping size classes together resulted in genetic panmixia across sites, but systematic removal of large individuals showed significant population-level differentiation and three separate population clusters among juveniles less than 260 cm total length. Tests for relatedness found that 8.9% of our sample set was composed of first-order related pairs (N = 16), including several full siblings from different litters, a sign of multi-cycle genetic monogamy which carries implications for effective population size. By mapping genetic assignments of juveniles, we identified a signature of fine-scale genetic structure suggesting broad biparental site fidelity to reproductive habitat in the northeast Gulf of Mexico, which is concordant with both genetic and tracking data. Taken together, these findings demonstrate how lumping individuals from different life stages in genetic studies may obscure fine-scale genetic structure, confounding future conservation efforts.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Severe tropical cyclones over southwest Pacific Islands: economic impacts and implications for disaster risk management - Anil Deo; Savin S. Chand; R. Duncan McIntosh; Bipen Prakash; Neil J. Holbrook; Andrew Magee; Alick Haruhiru; Philip Malsale (Climatic Change, 2022)
Tropical cyclones (TCs) are amongst the costliest natural hazards for southwest Pacific (SWP) Island nations. Extreme winds coupled with heavy rainfall and related coastal hazards, such as large waves and high seas, can have devastating consequences for life and property. Effects of anthropogenic climate change are likely to make TCs even more destructive in the SWP (as that observed particularly over Fiji) and elsewhere around the globe, yet TCs may occur less often. However, the underpinning science of quantifying future TC projections amid multiple uncertainties can be complex. The challenge for scientists is how to turn such technical knowledge framed around uncertainties into tangible products to inform decision-making in the disaster risk management (DRM) and disaster risk reduction (DRR) sector. Drawing on experiences from past TC events as analogies to what may happen in a warming climate can be useful. The role of science-based climate services tailored to the needs of the DRM and DRR sector is critical in this context. In the first part of this paper, we examine cases of historically severe TCs in the SWP and quantify their socio-economic impacts. The second part of this paper discusses a decision-support framework developed in collaboration with a number of agencies in the SWP, featuring science-based climate services that inform different stages of planning in national-level risk management strategies.

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Prevalence of sustainable and unsustainable use of wild species inferred from the IUCN Red List of Threatened Species - Sophie M. E. Marsh; Michael Hoffmann; Neil D. Burgess; Thomas M. Brooks; Daniel W. S. Challender; Patricia J. Cremona; Craig Hilton‐Taylor; Flore Lafaye de Micheaux; Gabriela Lichtenstein; Dilys Roe; Monika Böhm (Conservation Biology, 2022)
Unsustainable exploitation of wild species represents a serious threat to biodiversity and to the livelihoods of local communities and Indigenous peoples. However, managed, sustainable use has the potential to forestall extinctions, aid recovery, and meet human needs. We analyzed species‐level data for 30,923 species from 13 taxonomic groups on the International Union for Conservation of Nature Red List of Threatened Species to investigate patterns of intentional biological resource use. Forty percent of species (10,098 of 25,009 species from 10 data‐sufficient taxonomic groups) were used. The main purposes of use were pets, display animals, horticulture, and human consumption. Intentional use is currently contributing to elevated extinction risk for 28–29% of threatened or near threatened (NT) species (2752–2848 of 9753 species). Intentional use also affected 16% of all species used (1597–1631 of 10,098). However, 72% of used species (7291 of 10,098) were least concern, of which nearly half (3469) also had stable or improving population trends. The remainder were not documented as threatened by biological resource use, including at least 172 threatened or NT species with stable or improving populations. About one‐third of species that had use documented as a threat had no targeted species management actions to directly address this threat. To improve use‐related red‐list data, we suggest small amendments to the relevant classification schemes and required supporting documentation. Our findings on the prevalence of sustainable and unsustainable use, and variation across taxa, can inform international policy making, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, the Convention on Biological Diversity, and the Convention on International Trade in Endangered Species.

Atlantic mackerel ( Scomber scombrus ) change skin colour in response to crowding stress - Guro M. Tveit; Neil Anders; Morten S. Bondø; John R. Mathiassen; Mike Breen (Journal of Fish Biology, 2022)
Wild capture can be stressful for fish. Stress has the potential to induce mortality in released unwanted catches or negative flesh quality consequences in retained ones. Such effects compromise sustainable natural resource management and industry profitability. Mitigating stress during capture is therefore desirable. Biological indicators of stress can objectively inform fishers as to the functional welfare status of catches during fishing operations. If they are to be of practical use in mitigating stress during wild capture events, such indicators must be quantifiable, respond rapidly, reflect the level of induced stress and be easily observable. Atlantic mackerel ( Scomber scombrus ) are extensively targeted by purse seine fisheries in European waters but are particularly vulnerable to stress. Excessive crowding in the net is thought to be the principal stress mechanism. There is therefore a need to develop indicators of crowding stress for this species so that catch welfare can be improved. Here, we demonstrate that S. scombrus exhibit a skin colour change from predominately green to predominately blue when exposed to crowding stress. In sea cage trials, we induced various degrees of stress in groups of wild‐caught S. scombrus by manipulating crowding density and its duration. Skin colour was quantified in air using digital photography. The colour change occurred rapidly (within the typical duration of crowding events in the fishery), and its magnitude was correlated to the severity and duration of crowding. Bluer fish were also associated with higher levels of plasma lactate. No appreciable colour change was observed in uncrowded (control) groups during the treatment period. Nonetheless, unstressed S. scombrus did turn blue S. scombrus and could therefore be used to improve welfare during wild capture fishing.

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Shine a light: Under-ice light and its ecological implications in a changing Arctic Ocean - Giulia Castellani; Gaëlle Veyssière; Michael Karcher; Julienne Stroeve; S. Neil Banas; A. Heather Bouman; S. Andrew Brierley; Stacey Connan; Finlo Cottier; Fabian Große; Laura Hobbs; Christian Katlein; et al. (Ambio, 2022)
The Arctic marine ecosystem is shaped by the seasonality of the solar cycle, spanning from 24-h light at the sea surface in summer to 24-h darkness in winter. The amount of light available for under-ice ecosystems is the result of different physical and biological processes that affect its path through atmosphere, snow, sea ice and water. In this article, we review the present state of knowledge of the abiotic (clouds, sea ice, snow, suspended matter) and biotic (sea ice algae and phytoplankton) controls on the underwater light field. We focus on how the available light affects the seasonal cycle of primary production (sympagic and pelagic) and discuss the sensitivity of ecosystems to changes in the light field based on model simulations. Lastly, we discuss predicted future changes in under-ice light as a consequence of climate change and their potential ecological implications, with the aim of providing a guide for future research.

Biogeochemical consequences of a changing Arctic shelf seafloor ecosystem - Christian März; Felipe S. Freitas; Johan C. Faust; Jasmin A. Godbold; Sian F. Henley; Allyson C. Tessin; Geoffrey D. Abbott; Ruth Airs; Sandra Arndt; David K. A. Barnes; Laura J. Grange; Neil D. Gray; et al. (Ambio, 2022)
Unprecedented and dramatic transformations are occurring in the Arctic in response to climate change, but academic, public, and political discourse has disproportionately focussed on the most visible and direct aspects of change, including sea ice melt, permafrost thaw, the fate of charismatic megafauna, and the expansion of fisheries. Such narratives disregard the importance of less visible and indirect processes and, in particular, miss the substantive contribution of the shelf seafloor in regulating nutrients and sequestering carbon. Here, we summarise the biogeochemical functioning of the Arctic shelf seafloor before considering how climate change and regional adjustments to human activities may alter its biogeochemical and ecological dynamics, including ecosystem function, carbon burial, or nutrient recycling. We highlight the importance of the Arctic benthic system in mitigating climatic and anthropogenic change and, with a focus on the Barents Sea, offer some observations and our perspectives on future management and policy.

Decreased bee emergence along an elevation gradient: Implications for climate change revealed by a transplant experiment - Lindsie M. McCabe; Clare E. Aslan; Neil S. Cobb (Ecology, 2022)
Bees experience differences in thermal tolerance based on their geographical range; however, there are virtually no studies that examine how overwintering temperatures may influence immature survival rates. Here, we conducted a transplant experiment along an elevation gradient to test for climate‐change effects on immature overwinter survival using movement along elevational gradient for a community of 26 cavity‐nesting bee species in the family Megachilidae along the San Francisco Peaks, Arizona elevational gradient. In each of three years, we placed nest blocks at three elevations, to be colonized by native Megachilidae. Colonized blocks were then (1) moved to lower (warmer) elevations; (2) moved to higher (cooler) elevations; or (3) left in their natal habitat (no change in temperature). Because Megachilidae occupy high elevations with colder temperatures more than any other family of bees, we predicted that emergence would decrease in nest blocks moved to lower elevations, but that we would find no differences in emergence when nest blocks were moved to higher elevations. We found three major results: (1) Bee species moved to lower (warmer) habitats exhibited a 30% decrease in emergence compared with species moved within their natal habitat. (2) Habitat generalists were more likely than habitat specialists to emerge when moved up or down in elevation regardless of their natal life zones. (3) At our highest elevation treatment, emergence increased when blocks were moved to higher elevations, indicating that at least some Megachilidae species can survive at colder temperatures. Our results suggest that direct effects of warming temperatures will have negative impacts on the overall survival of Megachilidae. Additionally, above the tree line, low availability of wood‐nesting resources is a probable limiting factor on bees moving up in elevation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Increased water use efficiency leads to decreased precipitation sensitivity of tree growth, but is offset by high temperatures - Kelly A. Heilman; Valerie M. Trouet; Soumaya Belmecheri; Neil Pederson; Melissa A. Berke; Jason S. McLachlan (Oecologia, 2021)
Both increases in temperature and changes in precipitation may limit future tree growth, but rising atmospheric CO 2 could offset some of these stressors through increased plant Water Use Efficiency (WUE). The net balance between the negative impacts of climate change and positive effects of CO 2 on tree growth is crucial for ecotones, where increased climate stress could drive mortality and shifts in range. Here, we quantify the effects of climate, stand structure, and rising CO 2 on both annual tree-ring growth increment and intrinsic WUE (iWUE) at a savanna-forest boundary in the Upper Midwest United States. Taking a Bayesian hierarchical modelling approach, we find that plant iWUE increased by ~ 16–23% over the course of the twentieth century, but on average, tree-ring growth increments do not significantly increase. Consistent with higher iWUE under increased CO 2 and recent wetting, we observe a decrease in sensitivity of tree growth to annual precipitation, leading to ~ 35–41% higher growth under dry conditions compared to trees of similar size in the past. However, an emerging interaction between summer maximum temperatures and annual precipitation diminishes the water-savings benefit under hot and dry conditions. This decrease in precipitation sensitivity, and the interaction between temperature and precipitation are strongest in open canopy microclimates, suggesting that stand structure may modulate response to future changes. Overall, while higher iWUE may provide some water savings benefits to growth under normal drought conditions, near-term future temperature increases combined with drought events could drive growth declines of about 50%.

Modeling Marsh Dynamics Using a 3-D Coupled Wave-Flow-Sediment Model - Tarandeep S. Kalra; Neil K. Ganju; Alfredo L. Aretxabaleta; Joel A. Carr; Zafer Defne; Julia M. Moriarty (Frontiers in Marine Science, 2021)
Salt marshes are dynamic biogeomorphic systems that respond to external physical factors, including tides, sediment transport, and waves, as well as internal processes such as autochthonous soil formation. Predicting the fate of marshes requires a modeling framework that accounts for these processes in a coupled fashion. In this study, we implement two new marsh dynamic processes in the 3-D COAWST (coupled-ocean-atmosphere-wave sediment transport) model. The processes added are the erosion of the marsh edge scarp caused by lateral wave thrust from surface waves and vertical accretion driven by biomass production on the marsh platform. The sediment released from the marsh during edge erosion causes a change in bathymetry, thereby modifying the wave-energy reaching the marsh edge. Marsh vertical accretion due to biomass production is considered for a single vegetation species and is determined by the hydroperiod parameters (tidal datums) and the elevation of the marsh cells. Tidal datums are stored at user-defined intervals as a hindcast (on the order of days) and used to update the vertical growth formulation. Idealized domains are utilized to verify the lateral wave thrust formulation and show the dynamics of lateral wave erosion leading to horizontal retreat of marsh edge. The simulations of Reedy and Dinner Creeks within the Barnegat Bay estuary system demonstrate the model capability to account for both lateral wave erosion and vertical accretion due to biomass production in a realistic marsh complex. The simulations show that vertical accretion is dominated by organic deposition in the marsh interior, whereas deposition of mineral estuarine sediments occurs predominantly along the channel edges. The ability of the model to capture the fate of the sediment can be extended to model to simulate the impacts of future storms and relative sea-level rise (RSLR) scenarios on salt-marsh ecomorphodynamics.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Social Network Analysis Reveals the Subtle Impacts of Tourist Provisioning on the Social Behavior of a Generalist Marine Apex Predator - David M. P. Jacoby; Bethany S. Fairbairn; Bryan S. Frazier; Austin J. Gallagher; Michael R. Heithaus; Steven J. Cooke; Neil Hammerschlag (Frontiers in Marine Science, 2021)
Shark dive ecotourism is a lucrative industry in many regions around the globe. In some cases, sharks are provisioned using bait, prompting increased research on how baited dives influence shark behavior and yielding mixed results. Effects on patterns of habitat use and movement seemly vary across species and locations. It is unknown, however, whether wide-ranging, marine apex predators respond to provisioning by changing their patterns of grouping or social behavior. We applied a tiered analytical approach (aggregation-gregariousness-social preferences) examining the impact of provisioning on the putative social behavior of tiger sharks ( Galeocerdo cuvier ) at a dive tourism location in The Bahamas. Using network inference on three years of acoustic tracking data from 48 sharks, we tested for non-random social structure between non-provisioned and provisioned monitoring sites resulting in 12 distinct networks. Generally considered a solitary nomadic predator, we found evidence of sociality in tiger sharks, which varied spatiotemporally. We documented periods of both random ( n = 7 networks) and non-random aggregation ( n = 5 networks). Three of five non-random aggregations were at locations unimpacted by provisioning regardless of season, one occurred at an active provisioning site during the dry season and one at the same receivers during the wet season when provision activity is less prevalent. Aggregations lasted longer and occurred more frequently at provisioning sites, where gregariousness was also more variable. While differences in gregariousness among individuals was generally predictive of non-random network structure, individual site preferences, size and sex were not. Within five social preference networks, constructed using generalized affiliation indices, network density was lower at provisioning sites, indicating lower connectivity at these locations. We found no evidence of size assortment on preferences. Our data suggest that sociality may occur naturally within the Tiger Beach area, perhaps due to the unusually high density of individuals there. This study demonstrates the existence of periodic social behavior, but also considerable variation in association between tiger sharks, which we argue may help to mitigate any long-term impacts of provisioning on this population. Finally, we illustrate the utility of combining telemetry and social network approaches for assessing the impact of human disturbance on wildlife behavior.

The genome of the gymnosperm Picea glauca encodes a single Nucleobase Cation Symporter 1 (PgNCS1) that displays a broad yet unique solute specificity profile - Mahanish J. Thapa; Laura Mack; Jessica R. Schein; Kevin A. Hunt; Candace R. Alexander; Neil P. Schultes; George S. Mourad (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Physiological markers suggest energetic and nutritional adjustments in male sharks linked to reproduction - Bianca S. Rangel; Neil Hammerschlag; James A. Sulikowski; Renata Guimarães Moreira (Oecologia, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

A nucleobase cation symporter 2, EaXanP, from Erwinia amylovora transports xanthine - Andrea M. Funk; Regan B. Huntley; George S. Mourad; Neil P. Schultes (Journal of Plant Pathology, 2021)

Contribution of social media to cetacean research in Southeast Asia: illuminating populations vulnerable to litter - Amber Coram; Neil Angelo S. Abreo; Robert P. Ellis; Kirsten F. Thompson (Biodiversity and Conservation, 2021)
Litter in the marine environment, in particular plastic, is a significant threat to marine megafauna. Cetaceans are known to ingest or become entangled in marine debris, likely impacting individuals and populations. Southeast Asia is a biodiversity hotspot and harbours a diverse cetacean assemblage. However, there are key knowledge gaps relating to the impact of litter in this region due the lack of experts to survey its vast coastlines. This study aims to address such gaps by using social media, gathering data from Facebook posts relating to cetacean strandings and litter across Southeast Asia between 2009 and 2019. Results show that at least 15 cetacean species have been negatively affected by litter, with ingestion most commonly affecting deep-diving species. Epipelagic and mesopelagic foragers were most vulnerable to entanglement. Davao in the Philippines was identified as a litter-related stranding hotspot. The Irrawaddy dolphin ( Orcaella brevirostris ) and pygmy sperm whale ( Kogia breviceps ) are particularly vulnerable to litter. The combination of social media and peer reviewed literature can help build a more complete picture of the spatial distribution of marine litter and the scale of the impact it has on cetacean populations. In this study we provide details of a valuable online tool for helping to understand the impact of marine litter on cetaceans and other charismatic species that are a focus of community engagement.

Pattern, style and timing of British–Irish Ice Sheet advance and retreat over the last 45 000 years: evidence from NW Scotland and the adjacent continental shelf - Tom Bradwell; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; David Small; Rachel K. Smedley; Margot H. Saher; Steven G. Moreton; Dayton Dove; S. Louise Callard; Geoff A. T. Duller; Alicia Medialdea; et al. (Journal of Quaternary Science, 2021)
Predicting the future response of ice sheets to climate warming and rising global sea level is important but difficult. This is especially so when fast‐flowing glaciers or ice streams , buffered by ice shelves, are grounded on beds below sea level. What happens when these ice shelves are removed? And how do the ice stream and the surrounding ice sheet respond to the abruptly altered boundary conditions? To address these questions and others we present new geological, geomorphological, geophysical and geochronological data from the ice‐stream‐dominated NW sector of the last British–Irish Ice Sheet (BIIS). The study area covers around 45 000 km 2 of NW Scotland and the surrounding continental shelf. Alongside seabed geomorphological mapping and Quaternary sediment analysis, we use a suite of over 100 new absolute ages (including cosmogenic‐nuclide exposure ages, optically stimulated luminescence ages and radiocarbon dates) collected from onshore and offshore, to build a sector‐wide ice‐sheet reconstruction combining all available evidence with Bayesian chronosequence modelling. Using this information we present a detailed assessment of ice‐sheet advance/retreat history, and the glaciological connections between different areas of the NW BIIS sector, at different times during the last glacial cycle. The results show a highly dynamic, partly marine, partly terrestrial, ice‐sheet sector undergoing large size variations in response to sub‐millennial‐scale climatic (Dansgaard–Oeschger) cycles over the last 45 000 years. Superimposed on these trends we identify internally driven instabilities, operating at higher frequency, conditioned by local topographic factors, tidewater dynamics and glaciological feedbacks during deglaciation. Specifically, our new evidence indicates extensive marine‐terminating ice‐sheet glaciation of the NW BIIS sector during Greenland Stadials 12 to 9 – prior to the main ‘Late Weichselian’ ice‐sheet glaciation. After a period of restricted glaciation, in Greenland Interstadials 8 to 6, we find good evidence for rapid renewed ice‐sheet build‐up in NW Scotland, with the Minch ice‐stream terminus reaching the continental shelf edge in Greenland Stadial 5, perhaps only briefly. Deglaciation of the NW sector took place in numerous stages. Several grounding‐zone wedges and moraines on the mid‐ and inner continental shelf attest to significant stabilizations of the ice‐sheet grounding line, or ice margin, during overall retreat in Greenland Stadials 3 and 2, and to the development of ice shelves. NW Lewis was the first substantial present‐day land area to deglaciate, in the first half of Greenland Stadial 3 at a time of globally reduced sea‐level c. 26 ka bp , followed by Cape Wrath at c. 24 ka bp. The topographic confinement of the Minch straits probably promoted ice‐shelf development in early Greenland Stadial 2, providing the ice stream with additional support and buffering it somewhat from external drivers. However, c. 20–19 ka bp , as the grounding‐line migrated into shoreward deepening water, coinciding with a marked change in marine geology and bed strength, the ice stream became unstable. We find that, once underway, grounding‐line retreat proceeded in an uninterrupted fashion with the rapid loss of fronting ice shelves – first in the west, then the east troughs – before eventual glacier stabilization at fjord mouths in NW Scotland by ~17 ka bp. Around the same time, ~19–17 ka bp , ice‐sheet lobes readvanced into the East Minch – possibly a glaciological response to the marine‐instability‐triggered loss of adjacent ice stream (and/or ice shelf) support in the Minch trough. An independent ice cap on Lewis also experienced margin oscillations during mid‐Greenland Stadial 2, with an ice‐accumulation centre in West Lewis existing into the latter part of Heinrich Stadial 1. Final ice‐sheet deglaciation of NW mainland Scotland was punctuated by at least one other coherent readvance at c. 15.5 ka bp , before significant ice‐mass losses thereafter. At the glacial termination, c. 14.5 ka bp , glaciers fed outwash sediment to now‐abandoned coastal deltas in NW mainland Scotland around the time of global Meltwater Pulse 1A. Overall, this work on the BIIS NW sector reconstructs a highly dynamic ice‐sheet oscillating in extent and volume for much of the last 45 000 years. Periods of expansive ice‐sheet glaciation dominated by ice‐streaming were interspersed with periods of much more restricted ice‐cap or tidewater/fjordic glaciation. Finally, this work indicates that the role of ice streams in ice‐sheet evolution is complex but mechanistically important throughout the lifetime of an ice sheet – with ice streams contributing to the regulation of ice‐sheet health but also to the acceleration of ice‐sheet demise via marine ice‐sheet instabilities.

Novel disease resistance gene paralogs created by CRISPR/Cas9 in soy - Ervin D. Nagy; Julia L. Stevens; Neil Yu; Chris S. Hubmeier; Nona LaFaver; Megan Gillespie; Brian Gardunia; Qianshun Cheng; Steven Johnson; Audrey L. Vaughn; Miguel E. Vega-Sanchez; Mingqui Deng; et al. (Plant Cell Reports, 2021)
Key message Novel disease resistance gene paralogues are generated by targeted chromosome cleavage of tandem duplicated NBS-LRR gene complexes and subsequent DNA repair in soybean. This study demonstrates accelerated diversification of innate immunity of plants using CRISPR. Abstract Nucleotide-binding-site-leucine-rich-repeat (NBS-LRR) gene families are key components of effector-triggered immunity. They are often arranged in tandem duplicated arrays in the genome, a configuration that is conducive to recombinations that will lead to new, chimeric genes. These rearrangements have been recognized as major sources of novel disease resistance phenotypes. Targeted chromosome cleavage by CRISPR/Cas9 can conceivably induce rearrangements and thus emergence of new resistance gene paralogues. Two NBS-LRR families of soy have been selected to demonstrate this concept: a four-copy family in the Rpp1 region (Rpp1L) and a large, complex locus, Rps1 with 22 copies. Copy-number variations suggesting large-scale, CRISPR/Cas9-mediated chromosome rearrangements in the Rpp1L and Rps1 complexes were detected in up to 58.8% of progenies of primary transformants using droplet-digital PCR. Sequencing confirmed development of novel, chimeric paralogs with intact open reading frames. These novel paralogs may confer new disease resistance specificities. This method to diversify innate immunity of plants by genome editing is readily applicable to other disease resistance genes or other repetitive loci.

Tropical cyclone contribution to extreme rainfall over southwest Pacific Island nations - Anil Deo; Savin S. Chand; Hamish Ramsay; Neil J. Holbrook; Simon McGree; Andrew Magee; Samuel Bell; Mulipola Titimaea; Alick Haruhiru; Philip Malsale; Silipa Mulitalo; Arieta Daphne; et al. (Climate Dynamics, 2021)
Southwest Pacific nations are among some of the worst impacted and most vulnerable globally in terms of tropical cyclone (TC)-induced flooding and accompanying risks. This study objectively quantifies the fractional contribution of TCs to extreme rainfall (hereafter, TC contributions) in the context of climate variability and change. We show that TC contributions to extreme rainfall are substantially enhanced during active phases of the Madden–Julian Oscillation and by El Niño conditions (particularly over the eastern southwest Pacific region); this enhancement is primarily attributed to increased TC activity during these event periods. There are also indications of increasing intensities of TC-induced extreme rainfall events over the past few decades. A key part of this work involves development of sophisticated Bayesian regression models for individual island nations in order to better understand the synergistic relationships between TC-induced extreme rainfall and combinations of various climatic drivers that modulate the relationship. Such models are found to be very useful for not only assessing probabilities of TC- and non-TC induced extreme rainfall events but also evaluating probabilities of extreme rainfall for cases with different underlying climatic conditions. For example, TC-induced extreme rainfall probability over Samoa can vary from ~ 95 to ~ 75% during a La Niña period, if it coincides with an active or inactive phase of the MJO, and can be reduced to ~ 30% during a combination of El Niño period and inactive phase of the MJO. Several other such cases have been assessed for different island nations, providing information that have potentially important implications for planning and preparing for TC risks in vulnerable Pacific Island nations.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

The importance of Indigenous Peoples’ lands for the conservation of terrestrial mammals - Christopher J. O'Bryan; Stephen T. Garnett; Julia E. Fa; Ian Leiper; Jose A. Rehbein; Álvaro Fernández‐Llamazares; Micha V. Jackson; Harry D. Jonas; Eduardo S. Brondizio; Neil D. Burgess; Catherine J. Robinson; Kerstin K. Zander; et al. (Conservation Biology, 2021)
Indigenous Peoples’ lands cover over one‐quarter of Earth's surface, a significant proportion of which is still free from industrial‐level human impacts. As a result, Indigenous Peoples and their lands are crucial for the long‐term persistence of Earth's biodiversity and ecosystem services. Yet, information on species composition on these lands globally remains largely unknown. We conducted the first comprehensive analysis of terrestrial mammal composition across mapped Indigenous lands based on data on area of habitat (AOH) for 4460 mammal species assessed by the International Union for Conservation of Nature. We overlaid each species’ AOH on a current map of Indigenous lands and found that 2695 species (60% of assessed mammals) had ≥10% of their ranges on Indigenous Peoples’ lands and 1009 species (23%) had >50% of their ranges on these lands. For threatened species, 473 (47%) occurred on Indigenous lands with 26% having >50% of their habitat on these lands. We also found that 935 mammal species (131 categorized as threatened) had ≥ 10% of their range on Indigenous Peoples’ lands that had low human pressure. Our results show how important Indigenous Peoples’ lands are to the successful implementation of conservation and sustainable development agendas worldwide.

Reconciling Behavioural, Bioenergetic, and Oceanographic Views of Bowhead Whale Predation on Overwintering Copepods at an Arctic Hotspot (Disko Bay, Greenland) - Neil S. Banas; Eva Friis Møller; Kristin L. Laidre; Malene Simon; Ingrid H. Ellingsen; Torkel Gissel Nielsen (Frontiers in Marine Science, 2021)
Bowhead whales ( Balaena mysticetus ) visit Disko Bay, West Greenland in winter and early spring to feed on Calanus spp., at a time of year when the copepods are still mostly in diapause and concentrated in near-bottom patches. Combining past observations of copepod abundance and distribution with detailed observations of bowhead whale foraging behaviour from telemetry suggests that if the whales target the highest-density patches, they likely consume 26–75% of the Calanus standing stock annually. A parallel bioenergetic calculation further suggests that the whales' patch selection must be close to optimally efficient at finding hotspots of high density copepods near the sea floor in order for foraging in Disko Bay to be a net energetic gain. Annual Calanus consumption by bowhead whales is similar to median estimates of consumption by each of three zooplankton taxa (jellies, chaetognaths, and predatory copepods), and much greater than the median estimate of consumption by fish larvae, as derived from seasonal abundance and specific ingestion rates from the literature. The copepods' self-concentration during diapause, far from providing a refuge from predation, is the behaviour that makes this strong trophic link possible. Because the grazing impact of the whales comes 6–10 months later than the annual peak in primary production, and because Disko Bay sits at the end of rapid advective pathways (here delineated by a simple numerical particle-tracking experiment), it is likely that these Calanus populations act in part as a long-distance energetic bridge between the whales and primary production hundreds or thousands of km away.

Sea ice decline drives biogeographical shifts of key Calanus species in the central Arctic Ocean - Elizaveta A. Ershova; Ksenia N. Kosobokova; Neil S. Banas; Ingrid Ellingsen; Barbara Niehoff; Nicole Hildebrandt; Hans‐Juergen Hirche (Global Change Biology, 2021)
In recent decades, the central Arctic Ocean has been experiencing dramatic decline in sea ice coverage, thickness and extent, which is expected to have a tremendous impact on all levels of Arctic marine life. Here, we analyze the regional and temporal changes in pan‐Arctic distribution and population structure of the key zooplankton species Calanus glacialis and C. hyperboreus in relation to recent changes in ice conditions, based on historical (1993–1998) and recent (2007–2016) zooplankton collections and satellite‐based sea ice observations. We found strong correlations between Calanus abundance/population structure and a number of sea ice parameters. These relationships were particularly strong for C. glacialis , with higher numbers being observed at locations with a lower ice concentration, a shorter distance to the ice edge, and more days of open water. Interestingly, early stages of C. hyperboreus followed the same trends, suggesting that these two species substantially overlap in their core distribution area in the Arctic Ocean. Calanus glacialis and C. hyperboreus have been historically classified as shelf versus basin species, yet we conclude that both species can inhabit a wide range of bottom depths and their distribution in the Arctic Ocean is largely shaped by sea ice dynamics. Our data suggest that the core distribution patterns of these key zooplankton are shifting northwards with retreating sea ice and changing climate conditions.

Insufficient potassium and sulfur supply threaten the productivity of perennial forage grasses in smallholder farms on tropical sandy soils - Joshua Neil Monty Philp; Peter S. Cornish; Kim Sok Heng Te; Richard W. Bell; Wendy Vance; Vanndy Lim; Xueling Li; Sukanya Kamphayae; Matthew D. Denton (Plant and Soil, 2021)

Effects of temperature on sexual development in steelhead, Oncorhynchus mykiss - Kathleen S. Cole; David L. G. Noakes; Neil Thompson; Michael Blouin; Bruce Morrison; Ryan B. Couture; Joseph O’Neil; Carl B. Schreck (Environmental Biology of Fishes, 2021)

Characterizing Marine Heatwaves in the Kerguelen Plateau Region - Zimeng Su; Gabriela S. Pilo; Stuart Corney; Neil J. Holbrook; Mao Mori; Philippe Ziegler (Frontiers in Marine Science, 2021)
Marine heatwaves (MHWs) are prolonged extreme oceanic warm water events. Globally, the frequency and intensity of MHWs have been increasing in recent years, and it is expected that this trend is reflected in the Kerguelen Plateau region. MHWs can negatively impact the structure of marine biodiversity, marine ecosystems, and commercial fisheries. Considering that the KP is a hot-spot for marine biodiversity, characterizing MHWs and their drivers for this region is important, but has not been performed. Here, we characterize MHWs in the KP region between January 1994 and December 2016 using a combination of remotely sensed observations and output from a publicly available model hindcast simulation. We describe a strong MHW event that starts during the 2011/2012 austral summer and persists through winter, dissipating in late 2012. During the winter months, the anomalous temperature signal deepens from the surface to a depth of at least 150 m. We show that downwelling-favorable winds occur in the region during these months. At the end of 2012, as the MHW dissipates, upwelling-favorable winds prevail. We also show that the ocean temperature on the KP is significantly correlated with key modes of climate variability. Over the KP, temperature at both the ocean surface and at a depth of 150 m correlates significantly with the Indian Ocean Dipole. To the south of the KP, temperature variations are significantly correlated with the El Niño Southern Oscillation, and to both the north and south of the KP, with the Southern Annular Mode. These results suggest there may be potential predictability in ocean temperatures, and their extremes, in the KP region. Strong MHWs, like the event in 2012, may be detrimental to the unique ecosystem of this region, including economically relevant species, such as the Patagonian Toothfish.

First insights into the vertical habitat use of the whitespotted eagle ray Aetobatus narinari revealed by pop‐up satellite archival tags - Lauran R. Brewster; Brianna V. Cahill; Miranda N. Burton; Cassady Dougan; Jeffrey S. Herr; Laura Issac Norton; Samantha A. McGuire; Marisa Pico; Elizabeth Urban‐Gedamke; Kim Bassos‐Hull; John P. Tyminski; Robert E. Hueter; et al. (Journal of Fish Biology, 2021)
The whitespotted eagle ray Aetobatus narinari is a tropical to warm‐temperate benthopelagic batoid that ranges widely throughout the western Atlantic Ocean. Despite conservation concerns for the species, its vertical habitat use and diving behaviour remain unknown. Patterns and drivers in the depth distribution of A. narinari were investigated at two separate locations, the western North Atlantic (Islands of Bermuda) and the eastern Gulf of Mexico (Sarasota, Florida, U.S.A.). Between 2010 and 2014, seven pop‐up satellite archival tags were attached to A. narinari using three methods: a through‐tail suture, an external tail‐band and through‐wing attachment. Retention time ranged from 0 to 180 days, with tags attached via the through‐tail method retained longest. Tagged rays spent the majority of time (82.85 ± 12.17% S.D.) within the upper 10 m of the water column and, with one exception, no rays travelled deeper than ~26 m. One Bermuda ray recorded a maximum depth of 50.5 m, suggesting that these animals make excursions off the fore‐reef slope of the Bermuda Platform. Individuals occupied deeper depths (7.42 ± 3.99 m S.D.) during the day versus night (4.90 ± 2.89 m S.D.), which may be explained by foraging and/or predator avoidance. Each individual experienced a significant difference in depth and temperature distributions over the diel cycle. There was evidence that mean hourly depth was best described by location and individual variation using a generalized additive mixed model approach. This is the first study to compare depth distributions of A. narinari from different locations and describe the thermal habitat for this species. Our study highlights the importance of region in describing A. narinari depth use, which may be relevant when developing management plans, whilst demonstrating that diel patterns appear to hold across individuals.

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

A Review of Overlapping Landscapes: Pseudoreplication or a Red Herring in Landscape Ecology? - Benjamin Zuckerberg; Jeremy M. Cohen; Laura A. Nunes; Jacy Bernath-Plaisted; John D. J. Clare; Neil A. Gilbert; Sofia S. Kozidis; Scott B. Maresh Nelson; Amy A. Shipley; Kimberly L. Thompson; André Desrochers (Current Landscape Ecology Reports, 2020)

Streptomyces buecherae sp. nov., an actinomycete isolated from multiple bat species - Paris S. Hamm; Christopher A. Dunlap; Michael W. Mullowney; Nicole A. Caimi; Neil L. Kelleher; Regan J. Thomson; Andrea Porras-Alfaro; Diana E. Northup (Antonie van Leeuwenhoek, 2020)

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

Wildfire and the ecological niche: Diminishing habitat suitability for an indicator species within semi‐arid ecosystems - Shawn T. O’Neil; Peter S. Coates; Brianne E. Brussee; Mark A. Ricca; Shawn P. Espinosa; Scott C. Gardner; David J. Delehanty (Global Change Biology, 2020)
Globally accelerating frequency and extent of wildfire threatens the persistence of specialist wildlife species through direct loss of habitat and indirect facilitation of exotic invasive species. Habitat specialists may be especially prone to rapidly changing environmental conditions because their ability to adapt lags behind the rate of habitat alteration. As a result, these populations may become increasingly susceptible to ecological traps by returning to suboptimal breeding habitats that were dramatically altered by disturbance. We demonstrate a multistage modeling approach that integrates habitat selection and survival during the key nesting life‐stage of a bird species of high conservation concern, the greater sage‐grouse ( Centrocercus urophasianus ; hereafter, sage‐grouse). We applied these spatially explicit models to a spatiotemporally robust dataset of sage‐grouse nest locations and fates across wildfire‐altered sagebrush ecosystems of the Great Basin ecoregion, western United States. Female sage‐grouse exhibited intricate habitat selection patterns that varied across regional gradients of ecological productivity among sagebrush communities, but often selected nest sites that disproportionately resulted in nest failure. For example, 23% of nests occurred in wildfire‐affected habitats characterized by reduced sagebrush cover and greater composition of invasive annual grasses. We found survival of nests was negatively associated with wildfire‐affected areas, but positively associated with higher elevations with increased ruggedness and overall shrub cover. Strong site fidelity likely drove sage‐grouse to continue nesting in habitats degraded by wildfire. Hence, increasing frequency and extent of wildfire may contribute disproportionately to reduced reproductive success by creating ecological traps that act as population sinks. Identifying such habitat mismatches between selection and survival facilitates deeper understanding of the mechanisms driving reduced geographic niche space and population decline at broad spatiotemporal scales, while guiding management actions to areas that would be most beneficial to the species.

Linking Chlorophyll Concentration and Wind Patterns Using Satellite Data in the Central and Northern California Current System - Hally B. Stone; Neil S. Banas; Parker MacCready; Raphael M. Kudela; Bridget Ovall (Frontiers in Marine Science, 2020)

Inflammatory responses to acute exercise during pulmonary rehabilitation in patients with COPD - Alex R. Jenkins; Neil S. Holden; Arwel W. Jones (European Journal of Applied Physiology, 2020)
Objective Pulmonary rehabilitation is a cornerstone treatment in the management of chronic obstructive pulmonary disease (COPD). Acute bouts of exercise can lead to short bursts of inflammation in healthy individuals. However, it is unclear how COPD patients respond to acute bouts of exercise. This study assessed inflammatory responses to exercise in COPD patients at the start (phase 1) and end (phase 2) of pulmonary rehabilitation. Methods Blood samples were collected before and after an acute exercise bout at the start (phase 1, n = 40) and end (phase 2, n = 27) of pulmonary rehabilitation. The primary outcome was change in fibrinogen concentrations. Secondary outcomes were changes in CRP concentrations, total/differential leukocyte counts, markers of neutrophil activation (CD11b, CD62L and CD66b), and neutrophil subsets (mature, suppressive, immature, progenitor). Results Acute exercise (phase 1) did not induce significant changes in fibrinogen ( p = 0.242) or CRP ( p = 0.476). Total leukocyte count [mean difference (MD), 0.5 ± 1.1 (10 9 L −1 ); p = 0.004], neutrophil count [MD, 0.4 ± 0.8 (10 9 L −1 ); p < 0.001], and immature neutrophils (MD, 0.6 ± 0.8%; p < 0.001) increased post-exercise. Neutrophil activation markers, CD11b ( p = 0.470), CD66b ( p = 0.334), and CD62L ( p = 0.352) were not significantly altered post-exercise. In comparison to the start of pulmonary rehabilitation (phase 2), acute exercise at the end of pulmonary rehabilitation led to a greater fibrinogen response (MD, 84 mg/dL (95% CI − 14, 182); p = 0.045). Conclusion An acute bout of exercise does not appear to induce significant alterations in the concentrations of inflammatory mediators but can increase white blood cell subsets post-exercise. A greater fibrinogen response to acute exercise is seen at the end of pulmonary rehabilitation when compared to the start. Further research is required to understand the clinical context of these acute inflammatory responses to exercise.

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Eat or Sleep: Availability of Winter Prey Explains Mid-Winter and Spring Activity in an Arctic Calanus Population - Laura Hobbs; Neil S. Banas; Finlo R. Cottier; Jørgen Berge; Malin Daase (Frontiers in Marine Science, 2020)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Description and distribution of Desmacella hyalina sp. nov. (Porifera, Desmacellidae), a new cryptic demosponge in glass sponge reefs from the western coast of Canada - Lauren K. Law; Henry M. Reiswig; Bruce S. Ott; Neil McDaniel; Amanda S. Kahn; Keenan C. Guillas; Curtis Dinn; Sally P. Leys (Marine Biodiversity, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Addressing inequality and intolerance in human–wildlife coexistence - Neil R. Jordan; Bradley P. Smith; Robert G. Appleby; Lily M. van Eeden; Hugh S. Webster (Conservation Biology, 2020)
Millennia of human conflict with wildlife have built a culture of intolerance toward wildlife among some stakeholders. We explored 2 key obstacles to improved human–wildlife coexistence: coexistence inequality (how the costs and benefits of coexisting with wildlife are unequally shared) and intolerance. The costs of coexisting with wildlife are often disproportionately borne by the so‐called global south and rural communities, and the benefits often flow to the global north and urban dwellers. Attitudes and behaviors toward wildlife (tolerance versus intolerance) vary with social and cultural norms. We suggest more empathetic advocacy is needed that, for example, promotes conservation while appropriately considering those who bear the costs of conflict with wildlife. To achieve more equitable cost‐sharing, we suggest limiting the costs incurred by those most affected or by sharing those costs more widely. For example, we advocate for the development of improved wildlife compensation schemes, increasing the scale of rewilding efforts, and preventing wildlife‐derived revenue leaching out of the local communities bearing the costs of coexistence.

Inhibition of Erwinia amylovora by Bacillus nakamurai - Timothy D. Leathers; Lauren P. Saunders; Michael J. Bowman; Neil P. J. Price; Kenneth M. Bischoff; Joseph O. Rich; Christopher D. Skory; Melinda S. Nunnally (Current Microbiology, 2020)

Global Sensitivity Analysis of the Rodgers and Rowland Model for Prediction of Tissue: Plasma Partitioning Coefficients: Assessment of the Key Physiological and Physicochemical Factors That Determine Small-Molecule Tissue Distribution - Estelle Yau; Andrés Olivares-Morales; Michael Gertz; Neil Parrott; Adam S. Darwich; Leon Aarons; Kayode Ogungbenro (The AAPS Journal, 2020)

Assessing Changes in Airflow and Energy Loss in a Progressive Tracheal Compression Before and After Surgical Correction - Qiwei Xiao; Raul Cetto; Denis J. Doorly; Alister J. Bates; Jan N. Rose; Charlotte McIntyre; Andrew Comerford; Gitta Madani; Neil S. Tolley; Robert Schroter (Annals of Biomedical Engineering, 2020)
The energy needed to drive airflow through the trachea normally constitutes a minor component of the work of breathing. However, with progressive tracheal compression, patient subjective symptoms can include severe breathing difficulties. Many patients suffer multiple respiratory co-morbidities and so it is important to assess compression effects when evaluating the need for surgery. This work describes the use of computational prediction to determine airflow resistance in compressed tracheal geometries reconstructed from a series of CT scans. Using energy flux analysis, the regions that contribute the most to airway resistance during inhalation are identified. The principal such region is where flow emerging from the zone of maximum constriction undergoes breakup and turbulent mixing. Secondary regions are also found below the tongue base and around the glottis, with overall airway resistance scaling nearly quadratically with flow rate. Since the anatomical extent of the imaged airway varied between scans—as commonly occurs with clinical data and when assessing reported differences between research studies—the effect of sub-glottic inflow truncation is considered. Analysis shows truncation alters the location of jet breakup and weakly influences the pattern of pressure recovery. Tests also show that placing a simple artificial glottis in the inflow to a truncated model can replicate patterns of energy loss in more extensive models, suggesting a means to assess sensitivity to domain truncation in tracheal airflow simulations.

Projected Marine Heatwaves in the 21st Century and the Potential for Ecological Impact - Eric C. J. Oliver; Michael T. Burrows; Markus G. Donat; Alex Sen Gupta; Lisa V. Alexander; Sarah E. Perkins-Kirkpatrick; Jessica A. Benthuysen; Alistair J. Hobday; Neil J. Holbrook; Pippa J. Moore; Mads S. Thomsen; Thomas Wernberg; et al. (Frontiers in Marine Science, 2019)

Utilization of In Vitro, In Vivo and In Silico Tools to Evaluate the pH-Dependent Absorption of a BCS Class II Compound and Identify a pH-Effect Mitigating Strategy - Christoph Gesenberg; Neil R. Mathias; Yan Xu; John Crison; Ishani Savant; Amy Saari; David J. Good; Jeffrey N. Hemenway; Ajit S. Narang; Richard R. Schartman; Naiyu Zheng; Adela Buzescu; et al. (Pharmaceutical Research, 2019)

Microplastics on the Menu: Plastics Pollute Indonesian Manta Ray and Whale Shark Feeding Grounds - Elitza S. Germanov; Andrea D. Marshall; I. Gede Hendrawan; Ryan Admiraal; Christoph A. Rohner; Janis Argeswara; Raka Wulandari; Mahardika R. Himawan; Neil R. Loneragan (Frontiers in Marine Science, 2019)

Overexpression of the MYB29 transcription factor affects aliphatic glucosinolate synthesis in Brassica oleracea - Diana L. Zuluaga; Neil S. Graham; Annett Klinder; A. E. Elaine van Ommen Kloeke; Angelo R. Marcotrigiano; Carol Wagstaff; Ruud Verkerk; Gabriella Sonnante; Mark G. M. Aarts (Plant Molecular Biology, 2019)

Effect of different doses of supervised aerobic exercise on heart rate recovery in inactive adults who are overweight or obese: results from E-MECHANIC - Christoph Höchsmann; James L. Dorling; John W. Apolzan; Neil M. Johannsen; Daniel S. Hsia; Timothy S. Church; Corby K. Martin (European Journal of Applied Physiology, 2019)

Spatio‐temporal patterns of tree growth as related to carbon isotope fractionation in European forests under changing climate - Tatiana A. Shestakova; Jordi Voltas; Matthias Saurer; Frank Berninger; Jan Esper; Laia Andreu‐Hayles; Valérie Daux; Gerhard Helle; Markus Leuenberger; Neil J. Loader; Valérie Masson‐Delmotte; Antonio Saracino; et al. (Global Ecology and Biogeography, 2019)
Aim The aim was to decipher Europe‐wide spatio‐temporal patterns of forest growth dynamics and their associations with carbon isotope fractionation processes inferred from tree rings as modulated by climate warming. Location Europe and North Africa (30‒70° N, 10° W‒35° E). Time period 1901‒2003. Major taxa studied Temperate and Euro‐Siberian trees. Methods We characterize changes in the relationship between tree growth and carbon isotope fractionation over the 20th century using a European network consisting of 20 site chronologies. Using indexed tree‐ring widths (TRW i ), we assess shifts in the temporal coherence of radial growth across sites (synchrony) for five forest ecosystems (Atlantic, boreal, cold continental, Mediterranean and temperate). We also examine whether TRW i shows variable coupling with leaf‐level gas exchange, inferred from indexed carbon isotope discrimination of tree‐ring cellulose (Δ 13 C i ). Results We find spatial autocorrelation for TRW i and Δ 13 C i extending over a maximum of 1,000 km among forest stands. However, growth synchrony is not uniform across Europe, but increases along a latitudinal gradient concurrent with decreasing temperature and evapotranspiration. Latitudinal relationships between TRW i and Δ 13 C i (changing from negative to positive southwards) point to drought impairing carbon uptake via stomatal regulation for water saving occurring at forests below 60° N in continental Europe. An increase in forest growth synchrony over the 20th century together with increasingly positive relationships between TRW i and Δ 13 C i indicate intensifying impacts of drought on tree performance. These effects are noticeable in drought‐prone biomes (Mediterranean, temperate and cold continental). Main conclusions At the turn of this century, convergence in growth synchrony across European forest ecosystems is coupled with coordinated warming‐induced effects of drought on leaf physiology and tree growth spreading northwards. Such a tendency towards exacerbated moisture‐sensitive growth and physiology could override positive effects of enhanced leaf intercellular CO 2 concentrations, possibly resulting in Europe‐wide declines of forest carbon gain in the coming decades.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

The Functional Response Ratio (FRR): advancing comparative metrics for predicting the ecological impacts of invasive alien species - Ross N. Cuthbert; James W. E. Dickey; Neil E. Coughlan; Patrick W. S. Joyce; Jaimie T. A. Dick (Biological Invasions, 2019)

Relationships between the distribution and abundance of the invasive faucet snail (Bithynia tentaculata) and environmental factors in Laurentian Great Lakes coastal wetlands - Neil T. Schock; Alexander J. Reisinger; Lindsey S. Reisinger; Matthew J. Cooper; Jan J. H. Cibrowski; Thomas M. Gehring; Ashley H. Moerke; Carl R. Ruetz; Donald G. Uzarski (Biological Invasions, 2019)

Symptom Expression of Mainstream and Specialty Potato Cultivars to Bacterial Ring Rot (Clavibacter sepedonicus) and Evaluation of in-Field Detection - Jonathan L. Whitworth; Rachel A. Selstedt; Alan A. G. Westra; Phil Nolte; Kasia Duellman; S. K. R. Yellareddygari; Neil C. Gudmestad (American Journal of Potato Research, 2019)

Contrasting Habitat Use and Population Dynamics of Reef Manta Rays Within the Nusa Penida Marine Protected Area, Indonesia - Elitza S. Germanov; Lars Bejder; Delphine B. H. Chabanne; Dharmadi Dharmadi; I. Gede Hendrawan; Andrea D. Marshall; Simon J. Pierce; Mike van Keulen; Neil R. Loneragan (Frontiers in Marine Science, 2019)

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Assessing structural uncertainty caused by different weighting methods on the Standardized Drought Vulnerability Index (SDVI) - Demetrios E. Tsesmelis; Panagiotis D. Oikonomou; Constantina G. Vasilakou; Nikolaos A. Skondras; Vassilia Fassouli; Stavros G. Alexandris; Neil S. Grigg; Christos A. Karavitis (Stochastic Environmental Research and Risk Assessment, 2019)

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

Consumer trophic positions respond variably to seasonally fluctuating environments - Bailey C. McMeans; Taku Kadoya; Thomas K. Pool; Gordon W. Holtgrieve; Sovan Lek; Heng Kong; Kirk Winemiller; Vittoria Elliott; Neil Rooney; Pascal Laffaille; Kevin S. McCann (Ecology, 2019)
The effects of environmental seasonality on food web structure have been notoriously understudied in empirical ecology. Here, we focus on seasonal changes in one key attribute of a food web, consumer trophic position. We ask whether fishes inhabiting tropical river–floodplain ecosystems behave as seasonal omnivores, by shifting their trophic positions in relation to the annual flood pulse, or whether they feed at the same trophic position all year, as much empirical work implicitly assumes. Using dietary data from the Tonle Sap Lake, Cambodia, and a literature review, we find evidence that some fishes, especially small piscivores, increased consumption of invertebrates and/or plant material during the wet season, as predicted. However, nitrogen stable isotope (δ 15 N) data for 26 Tonle Sap fishes, spanning a broader range of functional groups, uncovered high variation in seasonal trophic position responses among species (0 to ±0.52 trophic positions). Based on these findings, species respond to the flood pulse differently. Diverse behavioral responses to seasonality, underpinned by spatiotemporal variation at multiple scales, could be central for rerouting matter and energy flow in these dynamic ecosystems. Seasonally flexible foraging behaviors warrant further study given their potential influence on food web dynamics in a range of fluctuating environments.

Water–Health Nexus: Modeling the Pathways and Barriers to Water-Related Diseases - Neil S. Grigg (Water Resources Management, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Predicting potato tuber yield loss due to early blight severity in the Midwestern United States - S. K. R. Yellareddygari; Raymond J. Taylor; Julie S. Pasche; Anqing Zhang; Neil C. Gudmestad (European Journal of Plant Pathology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Effect of Soil Temperature, Injection Depth, and Rate of Metam Sodium Efficacy in Fine-Textured Soils with High Organic Matter on the Management of Verticillium Wilt of Potato - S. K. R. Yellareddygari; Neil C. Gudmestad (American Journal of Potato Research, 2018)

Performance of an elite, hybrid family of a northern × southern highbush cross (‘Draper’ × ‘Jewel’) - James F. Hancock; James W. Olmstead; Rachel A. Itle; Peter W. Callow; Stuart Neils-Kraft; Edmund J. Wheeler; Jozer Mangandi; Suneth S. Sooriyapathirana; Lisa J. Rowland; Ted A. Mackey; Nahla V. Bassil; Chad E. Finn (Euphytica, 2018)

Effects of caffeine on reaction time are mediated by attentional rather than motor processes - Christopher W. N. Saville; H. M. de Morree; Neil M. Dundon; S. M. Marcora; C. Klein (Psychopharmacology, 2018)

Structural identifiability for mathematical pharmacology: models of myelosuppression - Neil D. Evans; S. Y. Amy Cheung; James W. T. Yates (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Analysis of Potato Mop-Top Virus Survival Probability in Post-Harvest Storage - S. K. R. Yellareddygari; Owusu Domfeh; Francisco G. Bittara; Neil C. Gudmestad (American Journal of Potato Research, 2017)

Building capacity in biodiversity monitoring at the global scale - Dirk S. Schmeller; Monika Böhm; Christos Arvanitidis; Shannon Barber-Meyer; Neil Brummitt; Mark Chandler; Eva Chatzinikolaou; Mark J. Costello; Hui Ding; Jaime García-Moreno; Mike Gill; Peter Haase; et al. (Biodiversity and Conservation, 2017)

A Risk-Based Characterization of Sediment Contamination by Legacy and Emergent Contaminants of Concern in Coastal British Columbia, Canada - Carmen Morales-Caselles; Jean-Pierre W. Desforges; Neil Dangerfield; Peter S. Ross (Archives of Environmental Contamination and Toxicology, 2017)

Polychlorinated Biphenyl-Related Alterations of the Expression of Essential Genes in Harbour Seals (Phoca vitulina) from Coastal Sites in Canada and the United States - Marie Noël; Neil Dangerfield; Steve Jeffries; Dyanna Lambourn; Monique Lance; Caren Helbing; Michel Lebeuf; Peter S. Ross (Archives of Environmental Contamination and Toxicology, 2017)

Corrigendum: Flow and Coral Morphology Control Coral Surface pH: Implications for the Effects of Ocean Acidification - Neil C. S. Chan; Daniel Wangpraseurt; Michael Kühl; Sean R. Connolly (Frontiers in Marine Science, 2017)

Local Ecological Knowledge (LEK) on Fish Behavior Around Anchored FADs: the Case of Tuna Purse Seine and Ringnet Fishers from Southern Philippines - Edison D. Macusi; Neil Angelo S. Abreo; Ricardo P. Babaran (Frontiers in Marine Science, 2017)

Diffusion Tensor Tractography of the Cerebellar Peduncles in Prematurely Born 7-Year-Old Children - Eilon Shany; Terrie E. Inder; Sharon Goshen; Iris Lee; Jeffrey J. Neil; Christopher D. Smyser; Lex W. Doyle; Peter J. Anderson; Joshua S. Shimony (The Cerebellum, 2017)

Crop health and its global impacts on the components of food security - S. Savary; S. Bregaglio; L. Willocquet; D. Gustafson; D. Mason D’Croz; A. Sparks; N. Castilla; A. Djurle; C. Allinne; Mamta Sharma; V. Rossi; L. Amorim; et al. (Food Security, 2017)

Genomic epidemiology of Cryptococcus yeasts identifies adaptation to environmental niches underpinning infection across an African HIV / AIDS cohort - Mathieu Vanhove; Mathew A. Beale; Johanna Rhodes; Duncan Chanda; Shabir Lakhi; Geoffrey Kwenda; Sile Molloy; Natasha Karunaharan; Neil Stone; Thomas S. Harrison; Tihana Bicanic; Matthew C. Fisher (Molecular Ecology, 2017)
Emerging infections caused by fungi have become a widely recognized global phenomenon and are causing an increasing burden of disease. Genomic techniques are providing new insights into the structure of fungal populations, revealing hitherto undescribed fine‐scale adaptations to environments and hosts that govern their emergence as infections. Cryptococcal meningitis is a neglected tropical disease that is responsible for a large proportion of AIDS ‐related deaths across Africa; however, the ecological determinants that underlie a patient's risk of infection remain largely unexplored. Here, we use genome sequencing and ecological genomics to decipher the evolutionary ecology of the aetiological agents of cryptococcal meningitis, Cryptococcus neoformans and Cryptococcus gattii , across the central African country of Zambia. We show that the occurrence of these two pathogens is differentially associated with biotic (macroecological) and abiotic (physical) factors across two key African ecoregions, Central Miombo woodlands and Zambezi Mopane woodlands. We show that speciation of Cryptococcus has resulted in adaptation to occupy different ecological niches, with C. neoformans found to occupy Zambezi Mopane woodlands and C. gattii primarily recovered from Central Miombo woodlands. Genome sequencing shows that C. neoformans causes 95% of human infections in this region, of which over three‐quarters belonged to the globalized lineage VNI . We show that VNI infections are largely associated with urbanized populations in Zambia. Conversely, the majority of C. neoformans isolates recovered in the environment belong to the genetically diverse African‐endemic lineage VNB , and we show hitherto unmapped levels of genomic diversity within this lineage. Our results reveal the complex evolutionary ecology that underpins the reservoirs of infection for this, and likely other, deadly pathogenic fungi.

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Galectin-1 Reduces Neuroinflammation via Modulation of Nitric Oxide-Arginase Signaling in HIV-1 Transfected Microglia: a Gold Nanoparticle-Galectin-1 “Nanoplex” a Possible Neurotherapeutic? - Ravikumar Aalinkeel; Courtney S. Mangum; Eliane Abou-Jaoude; Jessica L. Reynolds; Maixian Liu; Karin Sundquist; Neil U. Parikh; Lee D. Chaves; Manoj J. Mammen; Stanley A. Schwartz; Supriya D. Mahajan (Journal of Neuroimmune Pharmacology, 2017)

Understanding the double peaked El Niño in coupled GCMs - Felicity S. Graham; Andrew T. Wittenberg; Jaclyn N. Brown; Simon J. Marsland; Neil J. Holbrook (Climate Dynamics, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Body size drives allochthony in food webs of tropical rivers - Timothy D. Jardine; Thomas S. Rayner; Neil E. Pettit; Dominic Valdez; Douglas P. Ward; Garry Lindner; Michael M. Douglas; Stuart E. Bunn (Oecologia, 2017)

Metabolic impact of 100% fruit juice consumption on antioxidant/oxidant status and lipid profiles of adults: An Evidence-Based review - Kristi Crowe-White; J. Scott Parrott; Kim S. Stote; Melissa Gutschall; Sue Benson-Davies; Elizabeth Droke; Carol E. O'Neil; Taylor Wolfram; Paula Ziegler (Critical Reviews in Food Science and Nutrition, 2017)

Copepod Life Strategy and Population Viability in Response to Prey Timing and Temperature: Testing a New Model across Latitude, Time, and the Size Spectrum - Neil S. Banas; Eva F. Møller; Torkel G. Nielsen; Lisa B. Eisner (Frontiers in Marine Science, 2016)

Natural hazards in Australia: sea level and coastal extremes - Kathleen L. McInnes; Christopher J. White; Ivan D. Haigh; Mark A. Hemer; Ron K. Hoeke; Neil J. Holbrook; Anthony S. Kiem; Eric C. J. Oliver; Roshanka Ranasinghe; Kevin J. E. Walsh; Seth Westra; Ron Cox (Climatic Change, 2016)

Go-stimuli proportion influences response strategy in a sustained attention to response task - Kyle M. Wilson; Kristin M. Finkbeiner; Neil R. de Joux; Paul N. Russell; William S. Helton (Experimental Brain Research, 2016)

Projected impacts of 21st century climate change on diapause in Calanus finmarchicus - Robert J. Wilson; Neil S. Banas; Michael R. Heath; Douglas C. Speirs (Global Change Biology, 2016)
Diapause plays a key role in the life cycle of high latitude zooplankton. During diapause, animals avoid starving in winter by living in deep waters where metabolism is lower and met by lipid reserves. Global warming is therefore expected to shorten the maximum potential diapause duration by increasing metabolic rates and by reducing body size and lipid reserves. This will alter the phenology of zooplankton, impact higher trophic levels and disrupt biological carbon pumps. Here, we project the impacts of climate change on the key North Atlantic copepod Calanus finmarchicus under IPCC RCP 8.5. Potential diapause duration is modelled in relation to body size and overwintering temperature. The projections show pronounced geographic variations. Potential diapause duration reduces by more than 30% in the Western Atlantic, whereas in the key overwintering centre of the Norwegian Sea it changes only marginally. Surface temperature rises, which reduce body size and lipid reserves, will have a similar impact to deep‐water changes on diapause in many regions. Because deep‐water warming lags that at the surface, animals in the Labrador Sea could offset warming impacts by diapausing in deeper waters. However, the ability to control diapause depth may be limited.

Ischaemic preconditioning does not alter the determinants of endurance running performance in the heat - Carl A. James; Ashley G. B. Willmott; Alan J. Richardson; Peter W. Watt; Neil S. Maxwell (European Journal of Applied Physiology, 2016)

Estimating behavior in a black box: how coastal oceanographic dynamics influence yearling Chinook salmon marine growth and migration behaviors - Brian J. Burke; James J. Anderson; Jessica A. Miller; Londi Tomaro; David J. Teel; Neil S. Banas; António M. Baptista (Environmental Biology of Fishes, 2016)

Dynamic, mechanistic, molecular‐level modelling of cyanobacteria: Anabaena and nitrogen interaction - Ferdi L. Hellweger; Neil D. Fredrick; Mark J. McCarthy; Wayne S. Gardner; Steven W. Wilhelm; Hans W. Paerl (Environmental Microbiology, 2016)
Summary Phytoplankton (eutrophication, biogeochemical) models are important tools for ecosystem research and management, but they generally have not been updated to include modern biology. Here, we present a dynamic, mechanistic, molecular‐level (i.e. gene, transcript, protein, metabolite) model of Anabaena – nitrogen interaction. The model was developed using the pattern‐oriented approach to model definition and parameterization of complex agent‐based models. It simulates individual filaments, each with individual cells, each with genes that are expressed to yield transcripts and proteins. Cells metabolize various forms of N, grow and divide, and differentiate heterocysts when fixed N is depleted. The model is informed by observations from 269 laboratory experiments from 55 papers published from 1942 to 2014. Within this database, we identified 331 emerging patterns, and, excluding inconsistencies in observations, the model reproduces 94% of them. To explore a practical application, we used the model to simulate nutrient reduction scenarios for a hypothetical lake. For a 50% N only loading reduction, the model predicts that N fixation increases, but this fixed N does not compensate for the loading reduction, and the chlorophyll a concentration decreases substantially (by 33%). When N is reduced along with P, the model predicts an additional 8% reduction (compared to P only).

Exercise duration-matched interval and continuous sprint cycling induce similar increases in AMPK phosphorylation, PGC-1α and VEGF mRNA expression in trained individuals - Conor W. Taylor; Stephen A. Ingham; Julie E. A. Hunt; Neil R. W. Martin; Jamie S. M. Pringle; Richard A. Ferguson (European Journal of Applied Physiology, 2016)

Preferred conservation policies of shark researchers - David S. Shiffman; Neil Hammerschlag (Conservation Biology, 2016)
There is increasing concern about the conservation status of sharks. However, the presence of numerous different (and potentially mutually exclusive) policies complicates management implementation and public understanding of the process. We distributed an online survey to members of the largest professional shark and ray research societies to assess member knowledge of and attitudes toward different conservation policies. Questions covered society member opinions on conservation and management policies, personal histories of involvement in advocacy and management, and perceptions of the approach of conservation nongovernmental organizations (NGOs) to shark conservation. One hundred and two surveys were completed (overall response rate 21%). Respondents considered themselves knowledgeable about and actively involved in conservation and management policy; a majority believed scientists have a responsibility to advocate for conservation (75%), and majorities have sent formal public comments to policymakers (54%) and included policy suggestions in their papers (53%). They believe sustainable shark fisheries are possible, are currently happening today (in a few places), and should be the goal instead of banning fisheries. Respondents were generally less supportive of newer limit‐based (i.e., policies that ban exploitation entirely without a species‐specific focus) conservation policy tools, such as shark sanctuaries and bans on the sale of shark fins, than of target‐based fisheries management tools (i.e., policies that allow for sustainable harvest of species whose populations can withstand it), such as fishing quotas. Respondents were generally supportive of environmental NGO efforts to conserve sharks but raised concerns about some NGOs that they perceived as using incorrect information and focusing on the wrong problems. Our results show there is an ongoing debate in shark conservation and management circles relative to environmental policy on target‐based natural resources management tools versus limit‐based conservation tools. They also suggest that closer communication between the scientific and environmental NGO communities may be needed to recognize and reconcile differing values and objectives between these groups.

Evolution of Mid-Atlantic Coastal and Back-Barrier Estuary Environments in Response to a Hurricane: Implications for Barrier-Estuary Connectivity - Jennifer L. Miselis; Brian D. Andrews; Robert S. Nicholson; Zafer Defne; Neil K. Ganju; Anthony Navoy (Estuaries and Coasts, 2016)

Spawn date explains variation in growth rate among families of hatchery reared Hood River steelhead (Oncorhynchus mykiss) - Neil F. Thompson; Mark R. Christie; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Increased stem density and competition may diminish the positive effects of warming at alpine treeline - Yafeng Wang; Neil Pederson; Aaron M. Ellison; Hannah L. Buckley; Bradley S. Case; Eryuan Liang; J. Julio Camarero (Ecology, 2016)
The most widespread response to global warming among alpine treeline ecotones is not an upward shift, but an increase in tree density. However, the impact of increasing density on interactions among trees at treeline is not well understood. Here, we test if treeline densification induced by climatic warming leads to increasing intraspecific competition. We mapped and measured the size and age of Smith fir trees growing in two treelines located in the southeastern Tibetan Plateau. We used spatial point‐pattern and codispersion analyses to describe the spatial association and covariation among seedlings, juveniles, and adults grouped in 30‐yr age classes from the 1860s to the present. Effects of competition on tree height and regeneration were inferred from bivariate mark‐correlations. Since the 1950s, a rapid densification occurred at both sites in response to climatic warming. Competition between adults and juveniles or seedlings at small scales intensified as density increased. Encroachment negatively affected height growth and further reduced recruitment around mature trees. We infer that tree recruitment at the studied treelines was more cold‐limited prior to 1950 and shifted to a less temperature‐constrained regime in response to climatic warming. Therefore, the ongoing densification and encroachment of alpine treelines could alter the way climate drives their transitions toward subalpine forests.

Physical activity in older age: perspectives for healthy ageing and frailty - Jamie S. McPhee; David P. French; Dean Jackson; James Nazroo; Neil Pendleton; Hans Degens (Biogerontology, 2016)

Genetic isolation between coastal and fishery‐impacted, offshore bottlenose dolphin ( Tursiops spp.) populations - Simon J. Allen; Kate A. Bryant; Robert H. S. Kraus; Neil R. Loneragan; Anna M. Kopps; Alexander M. Brown; Livia Gerber; Michael Krützen (Molecular Ecology, 2016)
The identification of species and population boundaries is important in both evolutionary and conservation biology. In recent years, new population genetic and computational methods for estimating population parameters and testing hypotheses in a quantitative manner have emerged. Using a Bayesian framework and a quantitative model‐testing approach, we evaluated the species status and genetic connectedness of bottlenose dolphin ( Tursiops spp.) populations off remote northwestern Australia, with a focus on pelagic ‘offshore’ dolphins subject to incidental capture in a trawl fishery. We analysed 71 dolphin samples from three sites beyond the 50 m depth contour (the inshore boundary of the fishery) and up to 170 km offshore, including incidentally caught and free‐ranging individuals associating with trawl vessels, and 273 dolphins sampled at 12 coastal sites inshore of the 50 m depth contour and within 10 km of the coast. Results from 19 nuclear microsatellite markers showed significant population structure between dolphins from within the fishery and coastal sites, but also among dolphins from coastal sites, identifying three coastal populations. Moreover, we found no current or historic gene flow into the offshore population in the region of the fishery, indicating a complete lack of recruitment from coastal sites. Mitochondrial DNA corroborated our findings of genetic isolation between dolphins from the offshore population and coastal sites. Most offshore individuals formed a monophyletic clade with common bottlenose dolphins ( T. truncatus ), while all 273 individuals sampled coastally formed a well‐supported clade of Indo‐Pacific bottlenose dolphins ( T. aduncus ). By including a quantitative modelling approach, our study explicitly took evolutionary processes into account for informing the conservation and management of protected species. As such, it may serve as a template for other, similarly inaccessible study populations.

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Impact of 100% Fruit Juice Consumption on Diet and Weight Status of Children: An Evidence-based Review - Kristi Crowe-White; Carol E. O'Neil; J. Scott Parrott; Sue Benson-Davies; Elizabeth Droke; Melissa Gutschall; Kim s. Stote; Taylor Wolfram; Paula Ziegler (Critical Reviews in Food Science and Nutrition, 2016)

Ecosystem services in managing residential landscapes: priorities, value dimensions, and cross-regional patterns - K. L. Larson; K. C. Nelson; S. R. Samples; S. J. Hall; N. Bettez; J. Cavender-Bares; P. M. Groffman; M. Grove; J. B. Heffernan; S. E. Hobbie; J. Learned; J. L. Morse; et al. (Urban Ecosystems, 2016)

The solute specificity profiles of nucleobase cation symporter 1 (NCS1) from Zea mays and Setaria viridis illustrate functional flexibility - Micah Rapp; Jessica Schein; Kevin A. Hunt; Vamsi Nalam; George S. Mourad; Neil P. Schultes (Protoplasma, 2016)

Progress and Challenges in Coupled Hydrodynamic-Ecological Estuarine Modeling - Neil K. Ganju; Mark J. Brush; Brenda Rashleigh; Alfredo L. Aretxabaleta; Pilar del Barrio; Jason S. Grear; Lora A. Harris; Samuel J. Lake; Grant McCardell; James O’Donnell; David K. Ralston; Richard P. Signell; et al. (Estuaries and Coasts, 2016)

Angling for endangered fish: conservation problem or conservation action? - Steven J Cooke; Zeb S Hogan; Paul A Butcher; Michael J W Stokesbury; Rajeev Raghavan; Austin J Gallagher; Neil Hammerschlag; Andy J Danylchuk (Fish and Fisheries, 2016)
Recreational angling has been implicated in population declines of some marine and freshwater fish, but this activity is rarely considered as a threat or even halted when endangered species are targeted. Indeed, in some cases, anglers are drawn to fish for rare or endangered species. Conservation‐oriented behaviours such as catch‐and‐release are often practiced voluntarily due to the ethics of anglers, yet even in these cases, some fishing mortality occurs. Nonetheless, there are many indirect conservation benefits associated with recreational angling. Here, we present a series of case‐studies and consider whether catch‐and‐release angling for endangered fish is a conservation problem or a conservation action. If recreational angling activities contribute to population‐level consequences that are contrary to recovery strategies, then angling for endangered species would seem to be a poor option. However, as revealed by several case‐studies, there is much evidence that anglers are vocal and effective proponents of fish and habitat conservation, and for endangered species, they are often the only voice when other stakeholders are not engaged. Anglers may contribute directly to conservation actions via user fees (e.g. licences), philanthropic donations or by volunteering in research, education and restoration activities. However, it is important to quantify post‐release mortality as well as understand the full suite of factors influencing a given population or species to know the potential risks. A risk assessment approach outlined in the paper may be used by managers to determine when the benefits of angling for endangered species outweigh the risks.

The ecological and evolutionary stability of interspecific territoriality - Neil Losin; Jonathan P. Drury; Kathryn S. Peiman; Chaya Storch; Gregory F. Grether (Ecology Letters, 2016)
Interspecific territoriality may play an important role in structuring ecological communities, but the causes of this widespread form of interference competition remain poorly understood. Here, we investigate the phenotypic, ecological and phylogenetic correlates of interspecific territoriality in wood warblers (Parulidae). Interspecifically territorial species have more recent common ancestors and are more similar phenotypically, and are more likely to hybridise, than sympatric, non‐interspecifically territorial species. After phylogenetic corrections, however, similarity in plumage and territorial song are the only significant predictors of interspecific territoriality besides syntopy (fine‐scale geographic overlap). Our results do not support the long‐standing hypothesis that interspecific territoriality occurs only under circumstances in which niche divergence is restricted, which combined with the high incidence of interspecific territoriality in wood warblers (39% of species), suggests that this interspecific interaction is more stable, ecologically and evolutionarily, than commonly assumed.

Flow and Coral Morphology Control Coral Surface pH: Implications for the Effects of Ocean Acidification - Neil C. S. Chan; Daniel Wangpraseurt; Michael Kühl; Sean R. Connolly (Frontiers in Marine Science, 2016)

Climate Variation Overwhelms Efforts to Reduce Nitrogen Delivery to Coastal Waters - Neil D. Bettez; Jonathan M. Duncan; Peter M. Groffman; Lawrence E. Band; Jarlath O’Neil-Dunne; Sujay S. Kaushal; Kenneth T. Belt; Neely Law (Ecosystems, 2015)

Determinants of the t(14;18) translocation and their role in t(14;18)-positive follicular lymphoma - Rachel S. Kelly; Sandrine Roulland; Ester Morgado; Stéphanie Sungalee; Nathalie Jouve; Rosario Tumino; Vittorio Krogh; Salvatore Panico; Silvia Polidoro; Giovanna Masala; María-José Sánchez; Maria-Dolores Chirlaque; et al. (Cancer Causes & Control, 2015)

Managing Water Resources Conflicts: Modelling Behavior in a Decision Tool - Masih Akhbari; Neil S. Grigg (Water Resources Management, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

HSS revisited: multi‐channel processes mediate trophic control across a productivity gradient - Colette L. Ward; Kevin S. McCann; Neil Rooney (Ecology Letters, 2015)
Classical food web theory holds that energy channels are regulated by top‐down control with increasing productivity, arising from within‐channel processes. However, these hypotheses do not consider the existence of parallel energy channels linked by shared resource pools and which can fuel generalist predators, imposing trophic control arising from multi‐channel processes. Using 23 large marine food webs, we show that food web responses to increasing productivity are consistent with the apparent trophic cascade hypothesis ( ATCH ) – with rising productivity predators derive an increasing fraction of their diet from increasingly productive bottom‐up controlled detritus channels, thereby subsidising predator biomass, and in turn strengthening top‐down control in parallel grazing channels. These results testify to a fundamental role of detritus channels specifically and multi‐channel processes in general in mediating food web response to productivity and demonstrate that the ATCH provides an alternative explanation for classical predictions of top‐down control.

Two nights of sleep deprivation with or without energy restriction does not impair the thermal response to cold - Samuel J. Oliver; Adam D. Harper Smith; Ricardo J. S. Costa; Norbert Maassen; James L. J. Bilzon; Neil P. Walsh (European Journal of Applied Physiology, 2015)

Woodland recovery following drought‐induced tree mortality across an environmental stress gradient - Miranda D. Redmond; Neil S. Cobb; Michael J. Clifford; Nichole N. Barger (Global Change Biology, 2015)
Recent droughts and increasing temperatures have resulted in extensive tree mortality across the globe. Understanding the environmental controls on tree regeneration following these drought events will allow for better predictions of how these ecosystems may shift under a warmer, drier climate. Within the widely distributed piñon–juniper woodlands of the southwestern USA , a multiyear drought in 2002–2004 resulted in extensive adult piñon mortality and shifted adult woodland composition to a juniper‐dominated, more savannah‐type ecosystem. Here, we used pre‐ (1998–2001) and 10‐year post‐ (2014) drought stand structure data of individually mapped trees at 42 sites to assess the effects of this drought on tree regeneration across a gradient of environmental stress. We found declines in piñon juvenile densities since the multiyear drought due to limited new recruitment and high (>50%) juvenile mortality. This is in contrast to juniper juvenile densities, which increased over this time period. Across the landscape, piñon recruitment was positively associated with live adult piñon densities and soil available water capacity, likely due to their respective effects on seed and water availability. Juvenile piñon survival was strongly facilitated by certain types of nurse trees and shrubs. These nurse plants also moderated the effects of environmental stress on piñon survival: Survival of interspace piñon juveniles was positively associated with soil available water capacity, whereas survival of nursed piñon juveniles was negatively associated with perennial grass cover. Thus, nurse plants had a greater facilitative effect on survival at sites with higher soil available water capacity and perennial grass cover. Notably, mean annual climatic water deficit and elevation were not associated with piñon recruitment or survival across the landscape. Our findings reveal a clear shift in successional trajectories toward a more juniper‐dominated woodland and highlight the importance of incorporating biotic interactions and soil properties into species distribution modeling approaches.

The configural properties of task stimuli do influence vigilance performance - Neil R. de Joux; Kyle Wilson; Paul N. Russell; William S. Helton (Experimental Brain Research, 2015)

Problem Archetypes as Common Ground for Water Resources Management Education - Neil S. Grigg (Water Resources Management, 2015)

The evolution of authigenic Zn–Pb–Fe-bearing phases in the Grieves Siding peat, western Tasmania - Richelle Awid-Pascual; Vadim S. Kamenetsky; Karsten Goemann; Neil Allen; Taryn L. Noble; Bernd G. Lottermoser; Thomas Rodemann (Contributions to Mineralogy and Petrology, 2015)

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

Heterogeneity of Mitral Leaflet Matrix Composition and Turnover Correlates with Regional Leaflet Strain - Elizabeth H. Stephens; Patrick S. Connell; Monica M. Fahrenholtz; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Cellular and Extracellular Matrix Basis for Heterogeneity in Mitral Annular Contraction - Elizabeth H. Stephens; Monica M. Fahrenholtz; Patrick S. Connell; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Characteristics of the Tibetan Plateau snow cover variations based on daily data during 1997–2011 - Samuel S. P. Shen; Ruzhen Yao; Jazlynn Ngo; Alan M. Basist; Neil Thomas; Tandong Yao (Theoretical and Applied Climatology, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Aging and the mucosal immune system in the intestine - Neil A. Mabbott; Atsushi Kobayashi; Anuj Sehgal; Barry M. Bradford; Mari Pattison; David S. Donaldson (Biogerontology, 2015)

Heterozygote advantage at MHC DRB may influence response to infectious disease epizootics - Amy J. Osborne; John Pearson; Sandra S. Negro; B. Louise Chilvers; Martin A. Kennedy; Neil J. Gemmell (Molecular Ecology, 2015)
The effect of MHC polymorphism on individual fitness variation in the wild remains equivocal; however, much evidence suggests that heterozygote advantage is a major determinant. To understand the contribution of MHC polymorphism to individual disease resistance or susceptibility in natural populations, we investigated two MHC class II B loci, DQB and DRB , in the New Zealand sea lion ( NZSL , Phocarctos hookeri ). The NZSL is a threatened species which is unusually susceptible to death by bacterial infection at an early age; it has suffered three bacterial induced epizootics resulting in high mortality levels of young pups since 1997. The MHC DQB and DRB haplotypes of dead NZSL pups with known cause of death (bacteria, enteritis or trauma) were sequenced and reconstructed, compared to pups that survived beyond 2 months of age, and distinct MHC DRB allele frequency and genotype differences were identified. Two findings were striking: (i) one DRB allele was present only in dead pups, and (ii) one heterozygous DRB genotype, common in live pups, was absent from dead pups. These results are consistent with some functional relationship with these variants and suggest heterozygote advantage is operating at DRB . We found no association between heterozygosity and fitness at 17 microsatellite loci, indicating that general heterozygosity is not responsible for the effect on fitness detected here. This result may be a consequence of recurrent selection by multiple pathogen assault over recent years and highlights the importance of heterozygote advantage at MHC as a potential mechanism for fitness differences in wild populations.

Enzymatic modification of schizophyllan - Timothy D. Leathers; Nongnuch Sutivisedsak; Melinda S. Nunnally; Neil P. J. Price; April M. Stanley (Biotechnology Letters, 2015)

Phenological decoupling of mortality from wave forcing in kelp beds - Thibaut de Bettignies; Thomas Wernberg; Paul S. Lavery; Mathew A. Vanderklift; Jim R. Gunson; Graham Symonds; Neil Collier (Ecology, 2015)
Kelps often live in a harsh hydrodynamic environment where wave‐driven dislodgement of individuals can alter the biodiversity and functioning of reef systems, and increase production in coastal ecosystems adjacent to reefs. The current paradigm is that winter storms tear kelps from reefs once hydrodynamic forces exceed attachment or tissue strength—a threshold response that implies a pulsed relationship between wave forces and dislodgement. Here, we challenge this understanding by showing how kelp phenology can decouple susceptibility to dislodgement from seasonal patterns in wave forces. We measured kelp dislodgement rates and hydrodynamic forces at nine subtidal reefs over two years ( n = 4320 kelps tagged and monitored). Contrary to expectation, we found relatively low and constant dislodgement rates for all reefs (13% ± 6% [mean per season ± SD]) in spite of a strong temporal pattern in wave action and extreme water velocities (winter peaks up to 3–4 m/s). A biomechanical model, based on the balance between kelp attachment strength and hydrodynamic drag, demonstrated that severe reduction in individual kelp size toward winter (>50% decrease in biomass for all sites) minimized drag and made the kelps less susceptible to high water velocities, allowing individuals to survive storm velocities over 3–4 m/s. We conclude that the timing of reduced susceptibility to disturbance, through the seasonal reduction of individual kelp biomass that coincides with times of highest water velocities is critical to the dynamics of kelp dislodgement and survival. We propose that phenological processes maintain many kelp beds in a higher degree of population stability and equilibrium with hydrodynamic forces than previously believed.

Effects of supervised exercise on progression-free survival in lymphoma patients: an exploratory follow-up of the HELP Trial - Kerry S. Courneya; Christine M. Friedenreich; Conrado Franco-Villalobos; Jennifer J. Crawford; Neil Chua; Sanraj Basi; Mary K. Norris; Tony Reiman (Cancer Causes & Control, 2015)

Sex reversal, selection against hatchery females or wild males does not explain differences in sex ratio between first generation hatchery and wild steelhead, Oncorhynchus mykiss - Neil F. Thompson; Kathleen S. Cole; Laura A. McMahon; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2015)

Invasive alien species disrupt spatial and temporal ecology and threaten extinction in an insular, small mammal community - W. Ian Montgomery; Sally S. J. Montgomery; Neil Reid (Biological Invasions, 2015)

Spatial variability and temporal trends in water‐use efficiency of European forests - Matthias Saurer; Renato Spahni; David C. Frank; Fortunat Joos; Markus Leuenberger; Neil J. Loader; Danny McCarroll; Mary Gagen; Ben Poulter; Rolf T.W. Siegwolf; Laia Andreu‐Hayles; Tatjana Boettger; et al. (Global Change Biology, 2014)
The increasing carbon dioxide (CO 2 ) concentration in the atmosphere in combination with climatic changes throughout the last century are likely to have had a profound effect on the physiology of trees: altering the carbon and water fluxes passing through the stomatal pores. However, the magnitude and spatial patterns of such changes in natural forests remain highly uncertain. Here, stable carbon isotope ratios from a network of 35 tree‐ring sites located across Europe are investigated to determine the intrinsic water‐use efficiency ( iWUE ), the ratio of photosynthesis to stomatal conductance from 1901 to 2000. The results were compared with simulations of a dynamic vegetation model (LPX‐Bern 1.0) that integrates numerous ecosystem and land–atmosphere exchange processes in a theoretical framework. The spatial pattern of tree‐ring derived iWUE of the investigated coniferous and deciduous species and the model results agreed significantly with a clear south‐to‐north gradient, as well as a general increase in iWUE over the 20th century. The magnitude of the iWUE increase was not spatially uniform, with the strongest increase observed and modelled for temperate forests in Central Europe, a region where summer soil‐water availability decreased over the last century. We were able to demonstrate that the combined effects of increasing CO 2 and climate change leading to soil drying have resulted in an accelerated increase in iWUE . These findings will help to reduce uncertainties in the land surface schemes of global climate models, where vegetation–climate feedbacks are currently still poorly constrained by observational data.

Effectiveness of the Bjerknes stability index in representing ocean dynamics - Felicity S. Graham; Jaclyn N. Brown; Clothilde Langlais; Simon J. Marsland; Andrew T. Wittenberg; Neil J. Holbrook (Climate Dynamics, 2014)

Simulating Unstressed Crop Development and Growth Using the Unified Plant Growth Model (UPGM) - Gregory S. McMaster; James C. Ascough; Debora A. Edmunds; Larry E. Wagner; Fred A. Fox; Kendall C. DeJonge; Neil C. Hansen (Environmental Modeling & Assessment, 2014)

Convergent Surface Water Distributions in U.S. Cities - M. K. Steele; J. B. Heffernan; N. Bettez; J. Cavender-Bares; P. M. Groffman; J. M. Grove; S. Hall; S. E. Hobbie; K. Larson; J. L. Morse; C. Neill; K. C. Nelson; et al. (Ecosystems, 2014)

From Bench to Humans: Formulation Development of a Poorly Water Soluble Drug to Mitigate Food Effect - Preetanshu Pandey; Rhye Hamey; Dilbir S. Bindra; Zongyun Huang; Neil Mathias; Timothy Eley; John Crison; Brian Yan; Robert Perrone; Chandra Vemavarapu (AAPS PharmSciTech, 2014)

Hydrology and climatology at Laguna La Gaiba, lowland Bolivia: complex responses to climatic forcings over the last 25 000 years - SARAH E. METCALFE; BRONWEN S. WHITNEY; KATHARINE A. FITZPATRICK; FRANCIS E. MAYLE; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; DAVID G. MANN (Journal of Quaternary Science, 2014)
Diatom, geochemical and isotopic data provide a record of environmental change in Laguna La Gaiba, lowland Bolivia (17°45′S, 57°35′W), over the last ca. 25 000 years. High‐resolution diatom analysis around the Last Glacial–Interglacial Transition provides new insights into this period of change. The full and late glacial lake was generally quite shallow, but with evidence of periodic flooding. At about 13 100 cal a BP, just before the start of the Younger Dryas chronozone, the diatoms indicate shallower water conditions, but there is a marked change at about 12 200 cal a BP indicating the onset of a period of high variability, with rising water levels punctuated by periodic drying. From ca. 11 800 to 10 000 cal a BP, stable, deeper water conditions persisted. There is evidence for drying in the early to middle Holocene, but not as pronounced as that reported from elsewhere in the southern hemisphere tropics of South America. This was followed by the onset of wetter conditions in the late Holocene consistent with insolation forcing. Conditions very similar to present were established about 2100 cal a BP. A complex response to both insolation forcing and millennial‐scale events originating in the North Atlantic is noted.

Influence of Atrazine on the Scalation of Marcy’s Checkered Gartersnake, Thamnophis m. marcianus (Baird and Girard, 1853) - Ashley D. Walters; Katie Chamberlain; Neil B. Ford; John S. Placyk (Bulletin of Environmental Contamination and Toxicology, 2014)

Benefits of migration in relation to nutritional condition and predation risk in a partially migratory moose population - Kevin S. White; Neil L. Barten; Stacy Crouse; John Crouse (Ecology, 2014)
The costs and benefits of alternative migratory strategies are often framed in the context of top‐down and bottom‐up effects on individual fitness. This occurs because migration is considered a costly behavioral strategy that presumably confers explicit benefits to migrants in the form of either decreased predation risk (predation risk avoidance hypothesis) or increased nutrition (forage maturation hypothesis). To test these hypotheses, we studied a partially migratory moose ( Alces alces ) population and contrasted explicit measures of predation risk (i.e., offspring survival) and nutrition (i.e., accumulation of endogenous energy reserves) between resident and migratory subpopulations. We relied on data collected from migratory and nonmigratory radio‐marked moose ( n = 67) that inhabited a novel study system located in coastal Alaska between 2004 and 2010. In this area, 30% of the population resides year‐round on a coastal foreland area, while 48% migrate to either a small island archipelago or a subalpine ridge system (the remainder exhibited one of six different low‐occurrence strategies). Overall, we determined that accumulation of body fat during the growing season did not differ between migratory or resident modalities. However, calf survival was 2.6–2.9 times higher for individuals that migrated (survival, islands = 0.49 ± 0.16 [mean ± SE], n = 35; ridge = 0.52 ± 0.16, n = 33) than those that did not (survival, resident = 0.19 ± 0.08, n = 57). Our results support the predation risk avoidance hypotheses, and suggest that migration is a behavioral strategy that principally operates to reduce the risk of calf predation and does not confer explicit nutritional benefits. We did not directly detect trade‐offs between predation risk and nutrition for migratory individuals. Yet we identify an indirect life history mechanism that may mildly dampen the apparent fitness benefits of migration. The proximate factors accounting for differences in migration‐specific neonate survival are likely linked to accessibility of refugial habitats for moose at local and landscape scales, landscape factors that affect hunting efficacy of large carnivores, and interactions with rural human communities. Conservation of ungulate populations can be aided by integrating knowledge about migratory behavior, life history strategies, and factors that alter ungulate vulnerability, particularly those induced by human activity.

The Challenges of Incorporating Cultural Ecosystem Services into Environmental Assessment - Debra Satz; Rachelle K. Gould; Kai M. A. Chan; Anne Guerry; Bryan Norton; Terre Satterfield; Benjamin S. Halpern; Jordan Levine; Ulalia Woodside; Neil Hannahs; Xavier Basurto; Sarah Klain (Ambio, 2013)

A Framework for an Agent-Based Model to Manage Water Resources Conflicts - Masih Akhbari; Neil S. Grigg (Water Resources Management, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Comparing the performance of different stomatal conductance models using modelled and measured plant carbon isotope ratios (δ 13 C): implications for assessing physiological forcing - Per E. Bodin; Mary Gagen; Danny McCarroll; Neil J. Loader; Risto Jalkanen; Iain Robertson; Vincent R Switsur; John S. Waterhouse; Ewan J. Woodley; Giles H. F. Young; Paul B. Alton (Global Change Biology, 2013)
Accurate modelling of long‐term changes in plant stomatal functioning is vital to global climate change studies because changes in evapotranspiration influence temperature via physiological forcing of the climate. Various stomatal models are included in land surface schemes, but their robustness over longer timescales is difficult to validate. We compare the performance of three stomatal models, varying in their degree of complexity, and coupled to a land surface model. This is carried out by simulating the carbon isotope ratio of tree leaves (δ 13 C leaf ) over a period of 53 years, and comparing the results with carbon isotope ratios obtained from tree rings (δ 13 C stem ) measured at six sites in northern Europe. All three stomatal models fail to capture the observed interannual variability in the measured δ 13 C stem time series. However, the Soil‐Plant‐Atmosphere ( SPA ) model performs significantly better than the Ball‐Berry ( BB ) or COX models when tested for goodness‐of‐fit against measured δ 13 C stem . The δ 13 C leaf time series simulated using the SPA model are significantly positively correlated ( P SPA model underestimates interannual variability measured in δ 13 C stem , but is no worse than the BB model and significantly better than the COX model. The inability of current models to adequately replicate changes in stomatal response to rising levels of CO 2 concentrations, and thus to quantify the associated physiological forcing, warrants further investigation.

Quantification of Field Resistance to Verticillium dahliae in Eight Russet-Skinned Potato Cultivars Using Real-Time PCR - J. S. Pasche; A. L. Thompson; Neil C. Gudmestad (American Journal of Potato Research, 2013)

Differences in vulnerability to nicotine-induced kindling between female and male periadolescent rats - Patrícia Xavier L. Gomes; Gersilene V. de Oliveira; Fernanda Yvelize R. de Araújo; Glauce Socorro de Barros Viana; Francisca Cléa F. de Sousa; Thomas N. Hyphantis; Neil E. Grunberg; André F. Carvalho; Danielle S. Macêdo (Psychopharmacology, 2013)

Partial heat acclimation of athletes with spinal cord lesion - Paul C. Castle; B. Pasan Kularatne; John Brewer; Alexis R. Mauger; Ross A. Austen; James A. Tuttle; Nick Sculthorpe; Richard W. Mackenzie; Neil S. Maxwell; Anthony D. J. Webborn (European Journal of Applied Physiology, 2013)

Sensitivity of coral calcification to ocean acidification: a meta‐analysis - Neil C. S. Chan; Sean R. Connolly (Global Change Biology, 2013)
To date, meta‐analyses of effects of acidification have focused on the overall strength of evidence for statistically significant responses; however, to anticipate likely consequences of ocean acidification, quantitative estimates of the magnitude of likely responses are also needed. Herein, we use random effects meta‐analysis to produce a systematically integrated measure of the distribution of magnitudes of the response of coral calcification to decreasing Ω Arag . We also tested whether methodological and biological factors that have been hypothesized to drive variation in response magnitude explain a significant proportion of the among‐study variation. We found that the overall mean response of coral calcification is ~15% per unit decrease in Ω Arag over the range 2 Arag Arag ). Neither differences in carbonate chemistry manipulation method, study duration, irradiance level, nor study species growth rate explained a significant proportion of the among‐study variation. However, studies employing buoyant weighting found significantly smaller decreases in calcification per unit Ω Arag (~10%), compared with studies using the alkalinity anomaly technique (~25%). These differences may be due to the greater tendency for the former to integrate over light and dark calcification. If the existing body of experimental work is indeed representative of likely responses of corals in nature, our results imply that, under business as usual conditions, declines in coral calcification by end‐of‐century will be ~22%, on average, or ~15% if only studies integrating light and dark calcification are considered. These values are near the low end of published projections, but support the emerging view that variability due to local environmental conditions and species composition is likely to be substantial.

The effects of restoring a conifer Plantation on an Ancient Woodland Site (PAWS) in the UK on the habitat and local population of the Hazel Dormouse (Muscardinus avellanarius) - R. C. Trout; S. E. Brooks; P. Rudlin; J. Neil (European Journal of Wildlife Research, 2012)

First record of the Q Biotype of the sweetpotato whitefly, Bemisia tabaci, intercepted in the UK - Michelle E. Powell; Andrew G. S. Cuthbertson; Howard A. Bell; Neil Boonham; Jane Morris; Phil Northing (European Journal of Plant Pathology, 2012)

Effects of prenatal immune activation and peri-adolescent stress on amphetamine-induced conditioned place preference in the rat - Neil M. Richtand; Rebecca Ahlbrand; Paul S. Horn; Brad Chambers; Jon Davis; Stephen Benoit (Psychopharmacology, 2012)

Comment on Rosenberg and Garcia: Estimating displacement along the Brenner Fault and orogen-parallel extension in the Eastern Alps, Int J Earth Sci (Geol Rundsch) (2011) 100:1129–1145 - Bernhard Fügenschuh; Neil S. Mancktelow; Stefan S. Schmid (International Journal of Earth Sciences, 2012)

Major effect of retinal short-chain dehydrogenase reductase (RDHE2) on bovine fat colour - Rugang Tian; Neil G. Cullen; Chris A. Morris; Paul J. Fisher; Wayne S. Pitchford; Cynthia D. K. Bottema (Mammalian Genome, 2012)

Effect of daily mixed nutritional supplementation on immune indices in soldiers undertaking an 8-week arduous training programme - Bethany C. Diment; Matthew B. Fortes; Julie P. Greeves; Anna Casey; Ricardo J. S. Costa; Robert Walters; Neil P. Walsh (European Journal of Applied Physiology, 2012)

Case–control study of smoking and non-melanoma skin cancer - Dana E. Rollison; Michelle R. Iannacone; Jane L. Messina; L. Frank Glass; Anna R. Giuliano; Richard G. Roetzheim; Basil S. Cherpelis; Neil A. Fenske; Kristen A. Jonathan; Vernon K. Sondak (Cancer Causes & Control, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Effects of a nonnative, invasive lovegrass on Agave palmeri distribution, abundance, and insect pollinator communities - Denise L. Lindsay; Pamela Bailey; Richard F. Lance; Michael J. Clifford; Robert Delph; Neil S. Cobb (Biodiversity and Conservation, 2011)

Development and Implementation of a Forest Nursery Accreditation Policy at a Local Level in Leyte, Philippines - Rotacio S. Gravoso; Nestor O. Gregorio; Maria Anabelle D. Gerona; Moises Neil V. Seriño; Steve R. Harrison; Herville V. Pajaron; Jayson V. Godoy (Small-scale Forestry, 2011)

Efficiency of shoot regeneration from leaf, stem, petiole and petal explants of six cultivars of Chrysanthemum morifolium - Ju Yeon Song; Neil S. Mattson; Byoung Ryong Jeong (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Long-Term Tree Cover Dynamics in a Pinyon-Juniper Woodland: Climate-Change-Type Drought Resets Successional Clock - Michael J. Clifford; Neil S. Cobb; Michaela Buenemann (Ecosystems, 2011)

Detecting Alterations in Pulmonary Airway Development with Airway-by-Airway Comparison - DongYoub Lee; Neil Willits; Anthony S. Wexler (Annals of Biomedical Engineering, 2011)

Streptococcus uberis-specific T cells are present in mammary gland secretions of cows and can be activated to kill S. uberis - Michel Denis; S. Jane Lacy-Hulbert; Bryce M. Buddle; John H. Williamson; D. Neil Wedlock (Veterinary Research Communications, 2011)

Pressure Filtration of Australian Bagasse Pulp - Thomas J. Rainey; William O. S. Doherty; D. Mark Martinez; Richard J. Brown; Neil A. Kelson (Transport in Porous Media, 2011)

Application of GIS for Evaluation and Design of Watershed Guidelines - R. S. Bhalla; Neil W. Pelkey; K. V. Devi Prasad (Water Resources Management, 2011)

Prevalence of Mefenoxam Resistance Among Phytophthora erythroseptica Pethybridge Isolates in Minnesota and North Dakota - Chapara Venkataramana; Raymond J. Taylor; Julie S. Pasche; Neil. C. Gudmestad (American Journal of Potato Research, 2010)

The effects of space flight and microgravity on the growth and differentiation of PICM-19 pig liver stem cells - Neil C. Talbot; Thomas J. Caperna; LeAnn Blomberg; Paul G. Graninger; Louis S. Stodieck (In Vitro Cellular & Developmental Biology - Animal, 2010)

The effects of two nights of sleep deprivation with or without energy restriction on immune indices at rest and in response to cold exposure - Ricardo J. S. Costa; Adam Harper Smith; Samuel J. Oliver; Robert Walters; Norbert Maassen; James L. J. Bilzon; Neil Peter Walsh (European Journal of Applied Physiology, 2010)

Molecular cloning and localization of a calpain-like protease from the abdominal muscle of Norway lobster Nephrops norvegicus - S. G. Gornik; G. D. Westrop; G. H. Coombs; D. M. Neil (Molecular Biology Reports, 2010)

Climate change and human activities: a case study in Xinjiang, China - Zhuoting Wu; Hongjun Zhang; Crystal M. Krause; Neil S. Cobb (Climatic Change, 2010)

Genome-wide analysis of the chalcone synthase superfamily genes of Physcomitrella patens - P. K. Harshavardhan Koduri; Graeme S. Gordon; Elizabeth I. Barker; Che C. Colpitts; Neil W. Ashton; Dae-Yeon Suh (Plant Molecular Biology, 2010)

Wolverine gene flow across a narrow climatic niche - Michael K. Schwartz; Jeffrey P. Copeland; Neil J. Anderson; John R. Squires; Robert M. Inman; Kevin S. McKelvey; Kristy L. Pilgrim; Lisette P. Waits; Samuel A. Cushman (Ecology, 2009)
Wolverines ( Gulo gulo ) are one of the rarest carnivores in the contiguous United States. Effective population sizes in Montana, Idaho, and Wyoming, where most of the wolverines in the contiguous United States exist, were calculated to be 35 (credible limits, 28–52) suggesting low abundance. Landscape features that influence wolverine population substructure and gene flow are largely unknown. Recent work has identified strong associations between areas with persistent spring snow and wolverine presence and range. We tested whether a dispersal model in which wolverines prefer to disperse through areas characterized by persistent spring snow cover produced least‐cost paths among all individuals that correlated with genetic distance among individuals. Models simulating large preferences for dispersing within areas characterized by persistent spring snow explained the data better than a model based on Euclidean distance. Partial Mantel tests separating Euclidean distance from spring snow‐cover‐based effects indicated that Euclidean distance was not significant in describing patterns of genetic distance. Because these models indicated that successful dispersal paths followed areas characterized by spring snow cover, we used these understandings to derive empirically based least‐cost corridor maps in the U.S. Rocky Mountains. These corridor maps largely explain previously published population subdivision patterns based on mitochondrial DNA and indicate that natural colonization of the southern Rocky Mountains by wolverines will be difficult but not impossible.

Emitting Species in Chemiluminescence Reactions with Acidic Potassium Permanganate: A Re-Evaluation Based on New Spectroscopic Evidence - Jacqui L. Adcock; Paul S. Francis; Neil W. Barnett (Journal of Fluorescence, 2009)

One night of sleep deprivation decreases treadmill endurance performance - Samuel J. Oliver; Ricardo J. S. Costa; Stewart J. Laing; James L. J. Bilzon; Neil P. Walsh (European Journal of Applied Physiology, 2009)

Green Crab Larval Retention in Willapa Bay, Washington: An Intensive Lagrangian Modeling Approach - Neil S. Banas; P. Sean McDonald; David A. Armstrong (Estuaries and Coasts, 2009)

Successful spread of a biocontrol agent reveals a biosecurity failure: elucidating long distance invasion pathways for Gonatocerus ashmeadi in French Polynesia - Jérôme N. Petit; Mark S. Hoddle; Julie Grandgirard; George K. Roderick; Neil Davies (BioControl, 2009)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

Effects of saline root environment (NaCl) on nitrate and potassium uptake kinetics for rose plants: a Michaelis–Menten modelling approach - Daniele Massa; Neil S. Mattson; Heinrich J. Lieth (Plant and Soil, 2009)

Differential impact of adults and nymphs of a generalist predator on an exotic invasive pest demonstrated by molecular gut-content analysis - James D. Harwood; Ho Jung S. Yoo; Matthew H. Greenstone; Daniel L. Rowley; Robert J. O’Neil (Biological Invasions, 2009)

No effect of a 30-h period of sleep deprivation on leukocyte trafficking, neutrophil degranulation and saliva IgA responses to exercise - J. S. Costa Ricardo; Louise Cartner; Samuel J. Oliver; Stewart J. Laing; Robert Walters; James L. J. Bilzon; Neil P. Walsh (European Journal of Applied Physiology, 2009)

Local Participation in Natural Resource Monitoring: a Characterization of Approaches - FINN DANIELSEN; NEIL D. BURGESS; ANDREW BALMFORD; PAUL F. DONALD; MIKKEL FUNDER; JULIA P. G. JONES; PHILIP ALVIOLA; DANILO S. BALETE; TOM BLOMLEY; JUSTIN BRASHARES; BRIAN CHILD; MARTIN ENGHOFF; et al. (Conservation Biology, 2009)
The monitoring of trends in the status of species or habitats is routine in developed countries, where it is funded by the state or large nongovernmental organizations and often involves large numbers of skilled amateur volunteers. Far less monitoring of natural resources takes place in developing countries, where state agencies have small budgets, there are fewer skilled professionals or amateurs, and socioeconomic conditions prevent development of a culture of volunteerism. The resulting lack of knowledge about trends in species and habitats presents a serious challenge for detecting, understanding, and reversing declines in natural resource values. International environmental agreements require signatories undertake systematic monitoring of their natural resources, but no system exists to guide the development and expansion of monitoring schemes. To help develop such a protocol, we suggest a typology of monitoring categories, defined by their degree of local participation, ranging from no local involvement with monitoring undertaken by professional researchers to an entirely local effort with monitoring undertaken by local people. We assessed the strengths and weaknesses of each monitoring category and the potential of each to be sustainable in developed or developing countries. Locally based monitoring is particularly relevant in developing countries, where it can lead to rapid decisions to solve the key threats affecting natural resources, can empower local communities to better manage their resources, and can refine sustainable‐use strategies to improve local livelihoods. Nevertheless, we recognize that the accuracy and precision of the monitoring undertaken by local communities in different situations needs further study and field protocols need to be further developed to get the best from the unrealized potential of this approach. A challenge to conservation biologists is to identify and establish the monitoring system most relevant to a particular situation and to develop methods to integrate outputs from across the spectrum of monitoring schemes to produce wider indices of natural resources that capture the strengths of each.

Invasion dynamics of the glassy-winged sharpshooter Homalodisca vitripennis (Germar) (Hemiptera: Cicadellidae) in French Polynesia - Jérôme N. Petit; Mark S. Hoddle; Julie Grandgirard; George K. Roderick; Neil Davies (Biological Invasions, 2008)

A landscape theory for food web architecture - Neil Rooney; Kevin S. McCann; John C. Moore (Ecology Letters, 2008)
Ecologists have long searched for structures and processes that impart stability in nature. In particular, food web ecology has held promise in tackling this issue. Empirical patterns in food webs have consistently shown that the distributions of species and interactions in nature are more likely to be stable than randomly constructed systems with the same number of species and interactions. Food web ecology still faces two fundamental challenges, however. First, the quantity and quality of food web data required to document both the species richness and the interaction strengths among all species within food webs is largely prohibitive. Second, where food webs have been well documented, spatial and temporal variation in food web structure has been ignored. Conversely, research that has addressed spatial and temporal variation in ecosystems has generally ignored the full complexity of food web architecture. Here, we incorporate empirical patterns, largely from macroecology and behavioural ecology, into a spatially implicit food web structure to construct a simple landscape theory of food web architecture. Such an approach both captures important architectural features of food webs and allows for an exploration of food web structure across a range of spatial scales. Finally, we demonstrated that food webs are hierarchically organized along the spatial and temporal niche axes of species and their utilization of food resources in ways that stabilize ecosystems.

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2008)

NE-11 represents a new strain variant class of Potato virus Y - Jim Lorenzen; Phil Nolte; Darren Martin; Julie S. Pasche; Neil C. Gudmestad (Archives of Virology, 2008)

Engineering an invasion: classical biological control of the glassy-winged sharpshooter, Homalodisca vitripennis, by the egg parasitoid Gonatocerus ashmeadi in Tahiti and Moorea, French Polynesia - Julie Grandgirard; Mark S. Hoddle; Jerome N. Petit; George K. Roderick; Neil Davies (Biological Invasions, 2008)

Tracking the role of alternative prey in soybean aphid predation by Orius insidiosus : a molecular approach - JAMES D. HARWOOD; NICOLAS DESNEUX; HO JUNG S. YOO; DANIEL L. ROWLEY; MATTHEW H. GREENSTONE; JOHN J. OBRYCKI; ROBERT J. O′NEIL (Molecular Ecology, 2007)
The soybean aphid, Aphis glycines (Hemiptera: Aphididae), is a pest of soybeans in Asia, and in recent years has caused extensive damage to soybeans in North America. Within these agroecosystems, generalist predators form an important component of the assemblage of natural enemies, and can exert significant pressure on prey populations. These food webs are complex and molecular gut‐content analyses offer nondisruptive approaches for examining trophic linkages in the field. We describe the development of a molecular detection system to examine the feeding behaviour of Orius insidiosus (Hemiptera: Anthocoridae) upon soybean aphids, an alternative prey item, Neohydatothrips variabilis (Thysanoptera: Thripidae), and an intraguild prey species, Harmonia axyridis (Coleoptera: Coccinellidae). Specific primer pairs were designed to target prey and were used to examine key trophic connections within this soybean food web. In total, 32% of O. insidiosus were found to have preyed upon A. glycines , but disproportionately high consumption occurred early in the season, when aphid densities were low. The intensity of early season predation indicates that O. insidiosus are important biological control agents of A. glycines , although data suggest that N. variabilis constitute a significant proportion of the diet of these generalist predators. No Orius were found to contain DNA of H. axyridis , suggesting intraguild predation upon these important late‐season predators during 2005 was low. In their entirety, these results implicate O. insidiosus as a valuable natural enemy of A. glycines in this soybean agroecosystem.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic variation in catechol-O-methyltransferase (COMT) and obesity in the prostate, lung, colorectal, and ovarian (PLCO) cancer screening trial - Sophia S. Wang; Lindsay M. Morton; Andrew W. Bergen; Elizabeth Z. Lan; Nilanjan Chatterjee; Paul Kvale; Richard B. Hayes; Stephen J. Chanock; Neil E. Caporaso (Human Genetics, 2007)

Root, shoot tissues of Brassica juncea and Cereal secale promote potato health - Sieglinde S. Snapp; Kanchan U. Date; William Kirk; Katherine O’Neil; Amy Kremen; George Bird (Plant and Soil, 2007)

Resistance to phytophthora erythroseptica and pythium ultimum in a potato clone derived from s. berthaultii and s. etuberosum - Asunta L. Thompson; Raymond J. Taylor; Julie S. Pasche; Richard G. Novy; Neil C. Gudmestad (American Journal of Potato Research, 2007)

Systematic identification of factors involved in post-transcriptional processes in wheat grain - Sergiy Lopato; Ljudmilla Borisjuk; Andrew S. Milligan; Neil Shirley; Natalia Bazanova; Kate Parsley; Peter Langridge (Plant Molecular Biology, 2007)

Genes flanking Xist in mouse and human are separated on the X chromosome in American marsupials - Alexander I. Shevchenko; Irina S. Zakharova; Eugeny A. Elisaphenko; Nicolay N. Kolesnikov; Siobhan Whitehead; Christine Bird; Mark Ross; Jennifer R. Weidman; Randy L. Jirtle; Tatiana V. Karamysheva; Nicolay B. Rubtsov; John L. VandeBerg; et al. (Chromosome Research, 2007)

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2007)

Fatty acid synthase effects on bovine adipose fat and milk fat - Chris A. Morris; Neil G. Cullen; Belinda C. Glass; Dianne L. Hyndman; Tim R. Manley; Sharon M. Hickey; John C. McEwan; Wayne S. Pitchford; Cynthia D.K. Bottema; Michael A.H. Lee (Mammalian Genome, 2007)

HAIR SAMPLING AND GENOTYPING FROM HAIR FOLLICLES: A MINIMALLY‐INVASIVE ALTERNATIVE FOR GENETICS STUDIES IN SMALL, MOBILE PINNIPEDS AND OTHER MAMMALS - Abigail K. Caudron; Sandra S. Negro; Christopher G. Muller; Laura J. Boren; Neil J. Gemmell (Marine Mammal Science, 2007)

Systematic identification of factors involved in post-transcriptional processes in wheat grain - Sergiy Lopato; Ljudmilla Borisjuk; Andrew S. Milligan; Neil Shirley; Natalia Bazanova; Peter Langridge (Plant Molecular Biology, 2006)

Isometric handgrip training improves local flow-mediated dilation in medicated hypertensives - Cheri L. McGowan; Adrienne Visocchi; Martha Faulkner; Robin Verduyn; Mark Rakobowchuk; Andrew S. Levy; Neil McCartney; Maureen J. MacDonald (European Journal of Applied Physiology, 2006)

Interplasmid transposition demonstrates piggyBac mobility in vertebrate species - Neil F. Lobo; Tresa S. Fraser; John A. Adams; Malcolm J. Fraser (Genetica, 2006)

Palladium and gold removal and recovery from precious metal solutions and electronic scrap leachates by Desulfovibrio desulfuricans - Neil J. Creamer; Victoria S. Baxter-Plant; John Henderson; M. Potter; Lynne E. Macaskie (Biotechnology Letters, 2006)

Characterization of Households and its Implications for the Vegetation of Urban Ecosystems - J. M. Grove; A. R. Troy; J. P. M. O’Neil-Dunne; W. R. Burch; M. L. Cadenasso; S. T. A. Pickett (Ecosystems, 2006)

Co-production of Schizophyllan and Arabinoxylan from Corn Fiber - Timothy D. Leathers; Melinda S. Nunnally; Neil P. Price (Biotechnology Letters, 2006)

Antibody-based therapeutics: Focus on prostate cancer - Jeffrey S. Ross; Karen E. Gray; Iain J. Webb; Gary S. Gray; Mark Rolfe; David P. Schenkein; David M. Nanus; Mathew I. Millowsky; Neil H. Bander (Cancer and Metastasis Reviews, 2005)

Influence of tillage and method of metam sodium application on distribution and survival ofVerticillium dahliae in the soil and the development of verticillium wilt of potato - Raymond J. Taylor; Julie S. Pasche; Neil C. Gudmestad (American Journal of Potato Research, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Prolonged exposure of rats to intravenous methamphetamine: behavioral and neurochemical characterization - David S. Segal; Ronald Kuczenski; Meghan L. O’Neil; William P. Melega; Arthur K. Cho (Psychopharmacology, 2005)

Fourth meeting of the European Network of Research Tissue Banks – Future strategy to increase collaborations in the supply of human tissue for biomedical research - Samantha Orr; Eliane Alexandre; Brian J Clark; Neil Gray; Heiki Helin; Rivka Ravid; Mel Read; Lysiane Richert; Retlav Roosipuu; Ann-Cathrine Jonsson-Rylander; Carina Syring; Tambet Teesalu; et al. (Cell and Tissue Banking, 2005)

Patterns of Hg Bioaccumulation and Transfer in Aquatic Food Webs Across Multi-lake Studies in the Northeast US - Celia Y. Chen; Richard S. Stemberger; Neil C. Kamman; Brandon M. Mayes; Carol L. Folt (Ecotoxicology, 2005)

Relative Importance of Environmental Stress and Herbivory in Reducing Litter Fall in a Semiarid Woodland - Thomas D. Schuster; Neil S. Cobb; Thomas G. Whitham; Stephen C. Hart (Ecosystems, 2005)

Identification and analysis of safener-inducible expressed sequence tags in Populus using a cDNA microarray - A. S. Rishi; Shirin Munir; Vivek Kapur; Neil D. Nelson; Arun Goyal (Planta, 2004)

The role of polyp-stolon junctions in the redox signaling of colonial hydroids - Neil W. Blackstone; Kimberly S. Cherry; David H. Van Winkle (Hydrobiologia, 2004)

Elevated DNA-Protein Cross-Links in Red Blood Cells of German Carp, Cyprinus carpio, from the Lower Passaic River, New Jersey, USA - J. R. Kuykendall; S. J. O’Neil; E. J. Jarvi (Bulletin of Environmental Contamination and Toxicology, 2004)

Effects of age and mode of exercise on power output profiles during repeated sprints - Sbastien Ratel; Craig A. Williams; Jonathan Oliver; Neil Armstrong (European Journal of Applied Physiology, 2004)

CD45 variant alleles: possibly increased frequency of a novel exon 4 CD45 polymorphism in HIV seropositive Ugandans - Tara Stanton; Sally Boxall; Andrea Bennett; Pontiano Kaleebu; Christine Watera; Jimmy Whitworth; Neil French; Ritu Dawes; Adrian V. S. Hill; Walter Bodmer; Peter C. L. Beverley; Elma Z. Tchilian (Immunogenetics, 2004)

Combining Landsat ETM+ and Reef Check classifications for mapping coral reefs: a critical assessment from the southern Great Barrier Reef, Australia - K. E. Joyce; S. R. Phinn; C. M. Roelfsema; D. T. Neil; W. C. Dennison (Coral Reefs, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Influence of Oat Kernel Size and Size Distributions on Test Weight - Douglas C. Doehlert; Michael S. McMullen; Jean-Luc Jannink; Surangan Panigrahi; Huanzhong Gu; Neil Riveland (Cereal Research Communications, 2004)

Local tissue temperature effects on peak torque and muscular endurance during isometric knee extension - Leo J. Thornley; Neil S. Maxwell; Stephen S. Cheung (European Journal of Applied Physiology, 2003)

The regulation of virulence in phytopathogenic Erwinia species: quorum sensing, antibiotics and ecological considerations - Neil A. Whitehead; Joseph T. Byers; Paul Commander; Mark J. Corbett; Sarah J. Coulthurst; Lee Everson; Abigail K.P. Harris; Clare L. Pemberton; Natalie J.L. Simpson; Holly Slater; Debra S. Smith; Martin Welch; et al. (Antonie van Leeuwenhoek, 2002)

Near-infrared spectral imaging for quality assurance of pharmaceutical products: Analysis of tablets to assess powder blend homogeneity - Robbe C. Lyon; David S. Lester; E. Neil Lewis; Eunah Lee; Lawrence X. Yu; Everett H. Jefferson; Ajaz S. Hussain (AAPS PharmSciTech, 2002)

A new mouse mutant, skijumper - Majid Hafezparast; Simon Ball; Sharon J. Nicholson; Abi Witherden; Demet Arac; Neil Broadway; David Saggerson; Edwin Cooper; Mahmoud Naase; Stephen Gokhale; Patti Quant; Carol Lascelles; et al. (Mammalian Genome, 2002)

Wavelength-Resolved 3-Dimensional Fluorescence Lifetime Imaging - S. E. D. Webb; S. Lévêque-Fort; D. S. Elson; J. Siegel; T. Watson; M. J. Lever; M. Booth; R. Juskaitis; M. A. A. Neil; L. O. Sucharov; T. Wilson; P. M. W. French (Journal of Fluorescence, 2002)

Investigating the association between OPA1 polymorphisms and glaucoma: comparison between normal tension and high tension primary open angle glaucoma - Tin Aung; Louise Ocaka; Neil D. Ebenezer; Alex G. Morris; Glen Brice; Anne H. Child; Roger A. Hitchings; Ordan J. Lehmann; Shomi S. Bhattacharya (Human Genetics, 2002)

Factors influencing PVY development and disease expression in three potato cultivars - Martin D. Draper; Julie S. Pasche; Neil C. Gudmestad (American Journal of Potato Research, 2002)

Long-term sexual allocation in herbivore resistant and susceptible pinyon pine (Pinus edulis) - Neil S. Cobb; Robert T. Trotter; Thomas G. Whitham (Oecologia, 2002)

A major marker for normal tension glaucoma: association with polymorphisms in the OPA1 gene - Tin Aung; Louise Ocaka; Neil D. Ebenezer; Alex G. Morris; Michael Krawczak; Dawn L. Thiselton; Christiane Alexander; Marcela Votruba; Glen Brice; Anne H. Child; Peter J. Francis; Roger A. Hitchings; et al. (Human Genetics, 2002)

Uranyl precipitation by biomass from an enhanced biological phosphorus removal reactor - Neil Renninger; Katherine D. McMahon; Roger Knopp; Heino Nitsche; Douglas S. Clark; Jay D. Keasling (Biodegradation, 2001)

The DAV and Periadriatic fault systems in the Eastern Alps south of the Tauern window - Neil S. Mancktelow; Daniel F. Stöckli; Balz Grollimund; Wolfgang Müller; Bernhard Fügenschuh; Giulio Viola; Diane Seward; Igor M. Villa (International Journal of Earth Sciences, 2001)

Geochronological constraints on the evolution of the Periadriatic Fault System (Alps) - Wolfgang Müller; Giacomo Prosser; Neil S. Mancktelow; Igor M. Villa; Simon P. Kelley; Giulio Viola; Felix Oberli (International Journal of Earth Sciences, 2001)

Use of differential fluorescence induction and optical trapping to isolate environmentally induced genes - David Allaway; Neil A. Schofield; Mary E. Leonard; Liliana Gilardoni; Turlough M. Finan; Philip S. Poole (Environmental Microbiology, 2001)
The techniques of differential fluorescence induction (DFI) and optical trapping (OT) have been combined to allow the identification of environmentally induced genes in single bacterial cells. Designated DFI‐OT, this technique allows the in situ isolation of genes driving the expression of green fluorescent protein (Gfp) using temporal and spatial criteria. A series of plasmid‐based promoter probe vectors (pOT) was developed for the construction of random genomic libraries that are linked to gfpUV or egfp . Bacteria that do not express Gfp on laboratory medium (i.e. non‐fluorescent) were inoculated into the environment, and induced genes were detected with a combined fluorescence/optical trapping microscope. Using this selection strategy, rhizosphere‐induced genes with homology to thiamine pyrophosphorylase ( thiE ) and cyclic glucan synthase ( ndvB ) were isolated. Other genes were expressed late in the stationary phase or as a consequence of surface‐dependent growth, including fixND and metX , and a putative ABC transporter of putrescine. This strategy provides a unique ability to combine spatial, temporal and physical information to identify environmental regulation of bacterial gene expression.

Changes in Tissue Cellularity Are Associated with Growth Enhancement in Genetically Modified Arctic Char (Salvelinus alpinus L.) Carrying Recombinant Growth Hormone Gene - Tiina I. Pitkänen; Sheila Q. Xie; Aleksei Krasnov; Paul S. Mason; Hannu Mölsä; Neil C. Stickland (Marine Biotechnology, 2001)

Evidence that orexin-A-evoked grooming in the rat is mediated by orexin-1 (OX 1 ) receptors, with downstream 5-HT 2C receptor involvement - Mark S. Duxon; Jennifer Stretton; Kathryn Starr; Declan N.C. Jones; Vicky Holland; Graham Riley; Jeff Jerman; Stephen Brough; Darren Smart; Amanda Johns; Wai Chan; Rod A. Porter; et al. (Psychopharmacology, 2001)

Molecular Farming in Plants: A Current Perspective - A. S. Rishi; Neil D. Nelson; Arun Goyal (Journal of Plant Biochemistry and Biotechnology, 2001)

Optical traps: shedding light on biological processes - David Allaway; Neil A. Schofield; Philip S. Poole (Biotechnology Letters, 2000)

Prostate-specific Membrane Antigen (PSMA)-specific Monoclonal Antibodies in the Treatment of Prostate and Other Cancers - Michael C. Gong; Sam S. Chang; Michel Sadelain; Neil H. Bander; Warren D.W. Heston (Cancer and Metastasis Reviews, 1999)

Minimal requirements for in vitro reconstitution of the structural subunit of light-harvesting complexes of photosynthetic bacteria - John B. Todd; Paul A. Recchia; Pamela S. Parkes-Loach; John D. Olsen; Gregory J. S. Fowler; Peter McGlynn; C. Neil Hunter; Paul A. Loach (Photosynthesis Research, 1999)

The adenine pocket of a single catalytic site is derivatized when the bovine heart mitochondrial F1-ATPase is photoinactivated with 4-amino-1-octylquinaldinium - Neil B. Grodsky; William S. Allison (Cell Biochemistry and Biophysics, 1999)

The effects of the metal ions Mn 2+ and Co 2+ on muscle contraction in the Norway lobster Nephrops norvegicus (L.) - J. M. Holmes; A.-S. Gräns; D. M. Neil; S. P. Baden (Journal of Comparative Physiology B, 1999)

Anchoring of canine linkage groups with chromosome-specific markers - Petra Werner; Cathryn S. Mellersh; Michael G. Raducha; Susan DeRose; Gregory M. Acland; Ulana Prociuk; Neil Wiegand; Gustavo D. Aguirre; Paula S. Henthorn; Donald F. Patterson; Elaine A. Ostrander (Mammalian Genome, 1999)

Hypotension following mild bouts of resistance exercise and submaximal dynamic exercise - Jay R. MacDonald; J. Duncan MacDougall; Stephen A. Interisano; Kelly M. Smith; Neil McCartney; John S. Moroz; Ed V. Younglai; Mark A. Tarnopolsky (European Journal of Applied Physiology, 1999)

The redistribution of soil water by tree root systems - Stephen S. O. Burgess; Mark A. Adams; Neil C. Turner; Chin K. Ong (Oecologia, 1998)

Effects of stress on circulating nicotine and cotinine levels and in vitro nicotine metabolism in the rat - S. E. Winders; Neil E. Grunberg; Neal L. Benowitz; Alvito P. Alvares (Psychopharmacology, 1998)

An SEM study of porosity and grain boundary microstructure in quartz mylonites, Simplon Fault Zone, Central Alps - Neil S. Mancktelow; Djordje Grujic; Eric L. Johnson (Contributions to Mineralogy and Petrology, 1998)

Variable number tandem repeat polymorphism of the mucin genes located in the complex on 11p15.5 - Lynne E. Vinall; Alexander S. Hill; Pascal Pigny; Wendy S. Pratt; Neil Toribara; James R. Gum; Young S. Kim; Nicole Porchet; Jean-Pierre Aubert; D. M. Swallow (Human Genetics, 1998)

The Cystatin S gene maps to rat Chromosome 3, to which Dlmgh18 is re-assigned from Chromosome 1 - M. Beatriz Duran Alonso; Paul Shiels; Andrew S. McCallion; Neil K. Bennett; Anthony P. Payne; Josiane Szpirer; Claude Szpirer; Martin J. Brodie; R. Wayne Davies; Roger G. Sutciffe (Mammalian Genome, 1997)

A 54-kDa protein related to ras-guanine nucleotide release factor expressed in the rat exocrine pancreas - Pierre S. Tung; Neil P. Fam; Luping Chen; Michael F. Moran (Cell and Tissue Research, 1997)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)

Perceptual contributions to optimization of breathing - Yoshitaka Oku; Gerald M. Saidel; Murray D. Altose; Neil S. Cherniack (Annals of Biomedical Engineering, 1993)

Sensation and control of breathing: A dynamic model - Yoshitaka Oku; Gerald M. Saidel; Tatsuya Chonan; Murray D. Altose; Neil S. Cherniack (Annals of Biomedical Engineering, 1991)

Factors affecting respiratory system stability - Guy S. Longobardo; Neil S. Cherniack; Barbara Gothe (Annals of Biomedical Engineering, 1989)

The chemical control of respiration - Neil S. Cherniack; Guy S. Longobardo (Annals of Biomedical Engineering, 1981)

Possible optimization of respiratory controller sensitivity - Guy S. Longobardo; Neil S. Cherniack; Aniko Damokosh-Giordano (Annals of Biomedical Engineering, 1980)